Identification of potential mine sites for low-enthalpy geothermal energy extraction in Australia: a geospatial framework - C.S. Waravita; W.G.P. Kumari; J.S. Vinod; C. Jayasekara; Y. Han; R.K.S. Maleesha; L.T. White; P.G. Ranjith (Geothermics, 2026)

Technoeconomic and life-cycle assessment of multi-product and single-product lignocellulosic biorefineries - Seyedamirreza Babaei; Lauren Philips; Juhee Lee; Eun Joong Oh; Ye Huang; Adriana C. Neves; Yinglei Han; Jikai Zhao (Bioresource Technology, 2026)

Selective electrochemical recovery of rare-earth element europium with amine functionalized electrodes in capacitive deionization - Gabriela C. Martins; Youngwoo Choo; Riju Tyagi; Dong Suk Han; Ho Kyong Shon; Gayathri Naidu (Chemical Engineering Journal, 2026)

Unraveling the short- and long-term effects of lignocellulosic pretreatment derivatives on the anaerobic co-digestion of corn straw and food waste: Digester performance, microbial community, and metabolic mechanisms - Sifan Cao; Yong-Chen Han; Xiaochang C. Wang; Rong Chen; Bao-Shan Xing (Bioresource Technology, 2026)

Immune response as a modifier linking phthalate exposure to lung function decline: Results from a longitudinal study - Wei-Chi Wang; Yuan-Ting C. Lo; Hsiu-Ying Ku; Hsu-Kai Huang; You-Zhen Chen; Wei-Yu Lin; Han-Bin Huang (Environmental Pollution, 2026)

Organic matter in Martian radiation environment: Occurrence, evolutionary pathways, influence factors, characterization techniques, and further perspectives - Zhongyi Liu; Peixin Du; Meng Han; Enming Ju; David C. Fernández-Remolar; Ting Huang; Shaolin Li; Peng Yuan (Earth-Science Reviews, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Early Devonian chitinozoans from central Guangxi, South China - Shou-Han Wu; Yan Liang; Jian-Feng Lu; Sonia C. Camina (Review of Palaeobotany and Palynology, 2026)

Integrated AIS-meteorological data-driven ship berthing trajectory prediction based on deep learning approach - Diao Han; Yang Wang; Bing Wu; Haitong Xu; C. Guedes Soares (Ocean Engineering, 2026)

Experimental study of slamming load characteristics of an air-dropped AUV during water entry - Yuyang Cai; Hongfei Gao; Jianxuan Nong; Han Chen; C. Guedes Soares; Xueqian Zhou (Ocean Engineering, 2026)

Needle-like NiCo2S4 anchored on graphene-like carbon via ion-concentration regulation for hybrid supercapacitors - Jialong Li; Tong Han; C. Srinivasakannan; Shiye Cai; Gang Xue; Li Wang; Yaping Wang; Xinhui Duan (Chemical Engineering Journal, 2026)

ALKBH10B mediated epitranscriptomic regulation enhances drought tolerance of Arabidopsis thaliana via hormonal cross-talk and sustained photosynthesis - Yasira Shoaib; Rongpeng Han; Sabarna Bhattacharyya; Alexandra Finkenauer; Katharina Gutbrod; Peter Dörmann; Hunseung Kang; Ute C. Vothknecht; Fatima Chigri (Plant Cell Reports, 2026)
Key message The m⁶A demethylase ALKBH10B emerges as a crucial post-transcriptional regulator of hormonal crosstalk, photosynthetic maintenance, and mitochondrial energy metabolism to fine-tune plant stress adaptation to drought . Abstract Epitranscriptomic N⁶-methyladenosine (m⁶A) mRNA modification has emerged as an important regulatory layer of gene expression and protein synthesis in plant stress adaptation. In this study, expression profiling revealed that drought stress induces a global reprogramming of the m 6 A machinery in Arabidopsis thaliana , with the m 6 A demethylase ALKBH10B exhibiting a more pronounced time-dependent response. ALKBH10B transcription is induced by ABA, most likely via ABRE and MYB cis-elements, whereas jasmonate alleviates this activation. Moreover, ALKBH10B overexpressing plants (OX-1) accumulated wild type (WT) levels of ABA under drought stress but displayed a markedly reduced content in jasmonic acid (JA) and jasmonoyl-isoleucine (JA-Ile). They furthermore exhibit enhanced stomatal closure, improved water-use efficiency, and thus an enhanced drought tolerance. Transcriptome analysis revealed that drought stress induces fewer transcriptional changes in OX-1 plants compared to WT and the drought-sensitive alkbh10b-1 mutant. Differential expression and GO enrichment analyses highlight that photosynthesis-related processes were most affected by ALKBH10B activity, correlating with a preserved chlorophyll content and PSII efficiency in OX-1. Analysis by m⁶A-IP-qPCR showed that ALKBH10B directly demethylates specific photosynthesis-related and drought-responsive genes, while other transcripts are indirectly regulated by ALKBH10B-dependent processes. Moreover, transcripts associated with respiration were enriched in OX-1, indicating that ALKBH10B also supports mitochondrial energy metabolism during drought. Together, our results suggest that ALKBH10B enhances drought tolerance by coordinating m⁶A-dependent transcriptional and post-transcriptional regulation to maintain photosynthetic capacity and mitochondrial energy metabolism, as well as fine-tuning ABA-jasmonate crosstalk.

Morphology and Phylogeny of Hyalinostachys dehongensis sp. nov., a Bambusicolous Species From Yunnan Province, China - Yu‐Rong Yan; Li‐Su Han; Gang‐Ya Xu; Samantha C. Karunarathna; Nakarin Suwannarach; Jaturong Kumla; A. N. W. Sumedha Thushari; Sajad Ali; Dong‐Qin Dai; Saowaluck Tibpromma (New Zealand Journal of Botany, 2026)
China has abundant bamboo resources, among which Yunnan Province is one of the regions with the greatest number of species. The unique natural and geographic advantages provide an excellent environment for fungal growth. This study collected and isolated saprobic hyphomycetes associated with dead bamboo in Yunnan Province, China. Based on detailed morphological comparisons and multi‐locus phylogenetic analyses of combined LSU, ITS, tef 1‐ α , rpb 2, tub 2, and cmdA sequence data, the new isolates are introduced here as a novel species, Hyalinostachys dehongensis in the family Stachybotryaceae of Ascomycota. A complete description, morphological illustrations, and phylogenetic analysis results for the new species are provided. In addition, this species is introduced here as the second species since this genus was introduced in 2020.

Nigrospora spp. (Apiosporaceae) Associated With Diseased Rice Leaves in Guizhou Province, China - Jiajun Han; Danfeng Bao; Xingguo Tian; Milan C. Samarakoon (New Zealand Journal of Botany, 2026)
Plant pathogenic Nigrospora species have emerged as important threats to rice cultivation worldwide. During an ongoing survey of fungi associated with cultivated rice ( Oryza sativa L.) leaves in Guizhou Province, 11 Nigrospora isolates were recovered from 17 diseased leaf samples collected between April and June 2024. All isolates were obtained from rice leaf spots. Integration of detailed morphological observations with multilocus phylogenetic analyses based on three loci, namely internal transcribed spacer, translation elongation factor 1‐alpha, and partial β‐tubulin, demonstrated that the examined isolates represent five Nigrospora species: N. chinensis (one isolate), N. globospora (one isolate), N. musae (two isolates), N. oryzae (six isolates), and N. sphaerica (one isolate). This study represents the first report of N . globospora associated with rice. These findings provide new insights into the diversity and distribution of Nigrospora species associated with diseased rice leaves in Guizhou Province. In addition, this study provides an updated overview of Nigrospora species reported as plant pathogens, together with the plant diseases they cause and their known geographic distribution.

Examination of DNAm PhenoAge as an epigenetic biomarker for perioperative risk in adult spinal deformity surgeries - Michael P. Kelly; Jeffrey Hills; Justin S. Smith; Lawrence G. Lenke; Han Jo Kim; Shay Bess; Breton Line; Virginie Lafage; Renaud Lafage; Eric Klineberg; Ferran Pellise; Khaled Kebaish; et al. (GeroScience, 2026)

Targeting Mitochondrial Dysfunction in Acute Organophosphate Toxicity: A Preliminary Evaluation of Cyclosporine A - David H. Jang; Jarelis Cabrera; Jonathan Starr; Abigail Insana; Angela N. Viaene; John C. Greenwood; Frances S. Shofer; Johannes K. Ehinger; Shih-Han Kao; Todd J. Kilbaugh (Journal of Medical Toxicology, 2026)
Background Organophosphate (OP) compounds are widely used agricultural chemicals that pose significant public health and chemical threat concerns due to their neurotoxic effects. Although OP toxicity has classically been attributed to acetylcholinesterase inhibition and cholinergic crisis, emerging evidence suggests mitochondrial dysfunction may represent an additional and clinically relevant mechanism of injury. Experimental OP exposure has been associated with impaired electron transport chain activity, reduced ATP production, increased oxidative stress, and disruption of mitochondrial membrane integrity. However, there are currently no established mitochondrial-targeted therapies for OP poisoning. Diisopropyl fluorophosphate (DFP), a well-established OP surrogate, reproduces several neurologic and mitochondrial features of nerve agent exposure. Cyclosporine A (CsA), an inhibitor of the mitochondrial permeability transition pore (mPTP), may represent a potential mitochondrial-targeted intervention. Methods This preliminary translational study employed both in vitro and in vivo models to evaluate mitochondrial respiratory dysfunction following acute DFP exposure and to explore the feasibility of mitochondrial-targeted treatment paradigms using CsA. Human donor-derived peripheral blood mononuclear cells (PBMCs) were used for DFP and CsA dose-finding and mitochondrial respiratory characterization using high-resolution respirometry (Oroboros O2k) with standardized substrate–uncoupler–inhibitor titration (SUIT) protocols. In parallel, a non-survivor Sprague–Dawley rat model of acute DFP exposure was developed incorporating invasive hemodynamic monitoring, controlled ventilation, venous blood gas analysis, and CsA treatment paradigms administered either following DFP exposure or as pretreatment prior to exposure. Brain cortical homogenates were prepared for ex vivo respiratory assessment. Results Preliminary findings demonstrated that DFP exposure was descriptively associated with impaired mitochondrial respiration across multiple oxidative phosphorylation (OXPHOS)- and electron transport system (ETS)-linked respiratory states in both PBMC and rodent models. DFP exposure was additionally associated with physiologic and metabolic derangements, including acidosis and elevated lactate concentrations. Post-DFP CsA administration was associated with partial preservation of mitochondrial respiration across several respiratory states, while the Pre-DFP CsA group demonstrated respiratory profiles more closely approximating control values in select OXPHOS- and ETS-linked states, accompanied by relatively preserved physiologic and metabolic parameters. Conclusions These preliminary findings support the feasibility of integrating mitochondrial respiratory phenotyping into translational models of acute OP toxicity and further support investigation of mitochondrial-targeted strategies in OP-associated mitochondrial dysfunction. The observed respiratory and physiologic trends associated with CsA exposure, particularly in the pretreatment paradigm, provide an exploratory foundation for future preclinical studies evaluating mitochondrial-directed countermeasures in OP poisoning.

An interpretable Transformer-based deep learning model for ship berthing motion state prediction - Diao Han; Yang Wang; Haitong Xu; C. Guedes Soares; Bing Wu (Ocean Engineering, 2026)

Eight recommendations to enhance biodiversity outcomes of nature-based solutions at multiple scales - Charles B. van Rees; Collin VanBuren; Lori A. Han; Andrew Altieri; Matt Bilskie; James E. Byers; Jon Calabria; Matthew L. Chambers; Daniel J. Coleman; Katie Foster; Aliza Leit; Alec Nelson; et al. (Journal of Environmental Management, 2026)

Soil moisture information in Southeast Australia – A review of long-term field measurements toward enhanced monitoring and predictive applications - I.P. Senanayake; I.-Y. Yeo; M. Khaki; G.R. Hancock; P.G. Dahlhaus; N.J. Robinson; S.-C. Han; J.P. Walker (Geoderma Regional, 2026)

Application of optimized hydrothermal, ozone and superalkali pretreatment techniques for qualitative biogas production from corn straw: A comparative assessment - Sifan Cao; Yong-Chen Han; Huqe Farhana; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Fuel, 2026)

Long-term evolution of rainfall-induced deformation modes of granite slopes controlled by weathering progression - Xinyi Li; Qingjun Zuo; Lehua Wang; Xiaoliang Xu; Han Zhang; C. F. Lee; Biao Wang; Yanbing Tian (Landslides, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

In vitro ibuprofen has gene regulatory and anti-inflammatory properties in peripheral blood mononuclear cells of individuals with infection-provoked neurodevelopmental disorders - Velda X. Han; Jessica P. Hayes; Brian Gloss; Ruwani Dissanayake; Xianzhong Lau; Erica Tsang; Hiroya Nishida; Melanie Wong; Shekeeb S. Mohammad; Shrujna Patel; Russell C. Dale (Inflammopharmacology, 2026)
Gene-environment interactions, leading to immune-brain cross-talk and neuroinflammation are increasingly recognised in neurodevelopmental disorders (NDDs), such as autistic regression and paediatric acute onset neuropsychiatric syndrome (PANS). Nonsteroidal anti-inflammatory drugs, including ibuprofen, provides relief to some neuropsychiatric symptoms, however, the therapeutic mechanisms are unclear. We describe the benefit of ibuprofen in 18 children (11 males, ages 5–20 years) with infection-provoked deteriorations compatible with PANS (16/18) or autistic regression (7/18), five met criteria for both. Ibuprofen was well tolerated and led to improved emotional control, obsessive–compulsive symptoms, and aggression during infection-related exacerbations or the chronic phase. Single-cell RNA sequencing (scRNA-seq) was performed on peripheral blood mononuclear cells (PBMCs) in two children and their respective age-, sex- matched controls, before and after 24 h of in vitro ibuprofen and/or paracetamol incubation. A total of 45,134 cells were included. At baseline in both cases, there was dysregulation of immune pathways (response to virus, cell killing) and downregulation of ribosomal and translational pathways. Ibuprofen reversed the pro-inflammatory state in both children with reversal of cell killing pathways (granzyme genes) in Case 1, and reversal of viral pathways (interferon genes) in Case 2. Ibuprofen also reversed translation pathways (ribosomal protein genes), and regulation of translation (including EIF genes). In vitro paracetamol produced similar but weaker effects than ibuprofen. Children with infection-provoked neurodevelopmental episodes have baseline transcriptional and immune dysregulation in peripheral immune cells. We show that ibuprofen has transcriptional and anti-inflammatory effects, and that scRNA-seq in vitro-based studies can inform disease-modifying therapies for individuals with NDDs.

E-cigarette Aerosol Containing Nicotine Increases Aortic Stiffness in Young Mice - Pireyatharsheny Mulorz; Joscha Mulorz; Agnesa Mazrekaj; Hsiang-Han Liu; Wiebke Ibing; Joshua M. Spin; Lasse Bach Steffensen; Hans C. Beck; Uwe Raaz; Kensuke Toyama; Hubert Schelzig; Philip S. Tsao; et al. (Cardiovascular Toxicology, 2026)

Impact of polystyrene nanoplastics on soil microbial biomass - Chunyang Li; Heping Shang; Zeyu Cai; Weili Jia; Yini Cao; Xiupei Zhou; Jie Zhang; Sixiang Zhuang; Ziqin Lin; Anqi Liang; Lanfang Han; Jason C. White; et al. (Environmental Chemistry Letters, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mosquito-borne disease among individuals experiencing homelessness in the USA: a literature review - André B. B. Wilke; Megan D. Hill; Allisandra G. Kummer; Chalmers Vasquez; John-Paul Mutebi; Xi Huo; Han Li; Jing Chen; Shigui Ruan; John C. Beier; Maria Litvinova; Thomas Byrne; et al. (Journal of Pest Science, 2026)
Mosquito-borne diseases are a major public health issue. The USA has experienced mosquito-borne disease outbreaks, including West Nile virus, Zika, dengue, and malaria, highlighting widespread risk across the country. In the USA, exposure to mosquito vectors primarily occurs outdoors. Individuals experiencing unsheltered homelessness are particularly vulnerable to mosquito-borne diseases due to their increased exposure to mosquito vectors, limited access to healthcare, and high prevalence of underlying conditions. This review aims to examine the literature on mosquito-borne disease infections among individuals experiencing homelessness in the USA between 1999 and 2024. Our search strategy used Boolean methods on PubMed, Scopus, and Web of Science to select relevant publications. Two queries were used: the first query focused on individuals experiencing homelessness and mosquito-borne diseases, and the second one focused on epidemiological analyses of mosquito-borne disease outbreaks in the USA. Only studies reporting at least one infection among individuals experiencing homelessness were included. Our search resulted in the identification of 347 studies. After screening them, eight were ultimately included in this review. Half of the studies identified West Nile virus among individuals experiencing homelessness, and the other half reported cases of malaria. These studies show that individuals who spend more time outdoors, including individuals experiencing homelessness, may be at a greater risk of MBDs compared to the general population. However, the full extent of mosquito-borne disease exposure among individuals experiencing homelessness remains unclear. With climate change and globalization, there is a consensus in the literature showing an increasing risk of mosquito-borne disease transmission in the next decades, and we have already started to witness this increasing trend. Moreover, the USA is experiencing a steep increase in the overall nationwide homeless population. Therefore, we argue that developing policies aimed at providing homeless populations with housing during mosquito-borne disease outbreaks could be instrumental in protecting this segment of the population and promoting health equity.

Reliability and validity of the steep ramp test to assess cardiorespiratory fitness in apparently healthy adults - Ingeborg A. Trul-Kreuze; Bart C. Bongers; Darcy Ummels; Caspar Mylius; Anuschka S. Niemeijer; Tim Takken; Marianne K. Nieuwenhuis; Han Houdijk; Moniek Akkerman (European Journal of Applied Physiology, 2026)

A critical review of potential modifiers of air pollutant associations with dementia and related outcomes - JeongWon Han; Yina Li; Sangji Lee; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Melinda C. Power; Xiaohui Xu (NeuroToxicology, 2026)

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

Effects of carbon dioxide injection and modified atmosphere packaging on surface pigments and shelf life of ground beef - Sofiane Ghris; Inyee Han; James C. Acton; Ahmet Buyukyavuz; Julie K. Northcutt; Paul Dawson (Meat Science, 2026)

Transition to transpiration-dominated evapotranspiration on the Loess Plateau: spatially divergent driving mechanism and threshold effect after two decades of reforestation - Yongkang Xu; Depeng Zuo; Zhijin Ma; Jifeng Liu; Guoqing Wang; Zongxue Xu; Yuna Han; Karim C. Abbaspour; Hong Yang (Journal of Hydrology, 2026)

Evaluation for the machine learning based PM2.5 estimation using different spatial resolution of geostationary satellite AOD over megacities in Korea - Juhee Lee; Jhoon Kim; Yeseul Cho; Seoyoung Lee; Drew C. Pendergrass; Daniel J. Jacob; Hyunkwang Lim; Hahn Chul Jung; Kwang-Min Myung; Young-Doh Kim; Kyung Man Han; Ja-Ho Koo (Atmospheric Environment, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Early intestinal barrier changes in A53T transgenic Parkinson’s disease mice - Myat Noe Han; Olivia Artaiz; Matthew C. Rowe; David I. Finkelstein; Shanti Diwakarla; Rachel M. McQuade (Cell and Tissue Research, 2026)
Gut dysfunction commonly precedes motor symptoms in Parkinson’s disease (PD), but the mechanistic sequence of gut versus brain pathology remains unclear. This work aimed to define the timing of intestinal barrier dysfunction relative to central nervous system (CNS) changes in the A53T α-synuclein transgenic mouse model of PD. Functional and molecular assessments of the gastrointestinal tract (ileum and colon) were conducted at 12 and 36 weeks. We measured in vivo and ex vivo intestinal permeability, nutrient absorption, histomorphology, goblet cell density, and expression of MUC2 and Claudin-1. Inflammatory markers (CRP, TNF-α, CD45) were quantified in plasma and gut tissues. A53T mice exhibited increased intestinal permeability at 12 and 36 weeks, with transiently elevated ex vivo transepithelial electrical resistance (TER) at 12 weeks. Nutrient absorption remained intact. Morphological changes included widened villi and crypts, altered mucin expression, and early reductions in Claudin-1 in the ileum and the colon while inflammatory markers remained largely unchanged. These findings suggest that gut dysfunction precedes known central pathology in A53T mice, supporting further investigation into the gut as an early site of pathology and a potential therapeutic target in PD.

Astaxanthin, meclizine, mitoglitazone, pioglitazone, alpha-ketoglutarate, mifepristone, methotrexate, and atorvastatin-telmisartan do not increase lifespan in UM-HET3 mice - Ron Korstanje; Randy Strong; Adam B. Salmon; Molly A. Bogue; Sean P. Curran; Vivian Diaz; Elizabeth Fernandez; Brett Ginsburg; Melissa Han; David E. Harrison; Catherine Kaczorowski; Matt Kaeberlein; et al. (GeroScience, 2026)

Eco-hydrological response to climate and land surface changes based on eco-hydrological regionalization in the source region of the Yellow River - Yuna Han; Depeng Zuo; Zhijin Ma; Jifeng Liu; Guoqing Wang; Zongxue Xu; Karim C. Abbaspour; Hong Yang (Journal of Hydrology, 2026)

Soil temperature and aeration modification using black plastic mulch to improve potato yield and water use efficiency - Kaijing Yang; Fengxin Wang; Jianyu Zhao; Clinton C. Shock; Youliang Zhang; Shaoyuan Feng; Xiaoyan Hou; Jiangjiang Han; Xiuxia Wu (Field Crops Research, 2026)

The mechanism and performance of new CoFe2O4/MoS2/MIL-101(Fe) activated peroxymonosulfate for efficient degradation of tetracycline - C. Zhang; X. Hou; J. Wei; K. He; X. Han; C. Wang (International Journal of Environmental Science and Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Dissolved organic matter dynamics in a whale-dominated coastal system: Insights from Península Valdés, Argentina - Luis G. Egea; Rocío Jiménez-Ramos; Valeria C. D'Agostino; Mariana Degrati; Sebastián Giacomino; Guebuem Kim; Heejun Han; Rocío Loizaga (Marine Environmental Research, 2026)

Raising the bar: Deep learning on comprehensive database sets new benchmark for automated fission-track detection - Samuel C. Boone; Ling Chung; Noel Faux; Usha Nattala; Thomas Church; Chenghao Jiang; Malcolm McMillan; Sean Jones; David Liu; Han Jiang; Kris Ehinger; Tom Drummond; et al. (Computers & Geosciences, 2026)

Cumulative environmental exposures adversely impact social behaviour and are associated with dysregulation of genes and proteins involved in epigenetic, ribosomal, and immune regulation in male mice - Morgan C. Bucknor; Brooke A. Keating; Velda X. Han; Brian S. Gloss; Pinki Dey; Nader Aryamanesh; Lee L. Marshall; Mark E. Graham; Ruwani Dissanayake; Xianzhong Lau; Shrujna Patel; Stela P. Petkova; et al. (Inflammation Research, 2026)
Objective This study investigated how cumulative environmental exposures influence offspring behaviour and inflammation-related molecular signatures in the brain and peripheral immune system. Methods A novel "triple-hit" mouse model was developed using C57Bl/6JAusB mice (N = 70), combining preconceptual social stress, antenatal high-fat diet, and a postnatal immune challenge (poly(I:C), 10 mg/kg). At 12 weeks, offspring underwent behavioural tests relevant to neurodevelopmental disorders (NDDs), including the Elevated Plus Maze, 3-Chamber Social Preference, Self-Grooming, and Marble Burying. A composite NDD-risk index was calculated. Single-cell RNA sequencing (scRNA-seq) and bulk proteomics were performed on male triple-hit offspring to identify differentially expressed genes and proteins associated with inflammatory pathways. Results Male triple-hit offspring showed elevated NDD-related behavioural risk and social deficits, not observed in females. scRNA-seq revealed altered inflammatory and ribosomal pathways in brain glia and peripheral immune cells. Proteomic analysis showed decreased abundance of proteins involved in inflammation, translation, chromatin remodelling, and synaptic function in both brain and blood. Conclusion Combined environmental stressors may drive male-specific behavioural and inflammatory changes relevant to NDDs. The identification of overlapping inflammatory signatures in brain and peripheral immune cells supports a role for shared immune mechanisms in brain–immune axis dysfunction. However, these pathway-level findings should be interpreted as preliminary hypotheses and warrant independent validation to confirm their mechanistic significance.

A domain-adaptive deep neural network for real-time mooring tension prediction in floating wind turbines - Chaojun Yan; Wei Shi; Zhiyu Jiang; Xu Han; Xin Li; C. Guedes Soares (Ocean Engineering, 2026)

Photocatalytic ethylene scavenging by chitosan/gelatin packaging films loaded with TiO2-functionalized bismuth metal organic frameworks for postharvest preservation of fruits - Zohreh Riahi; Ajahar Khan; Su Jung Hong; Jong-Whan Rhim; Gye Hwa Shin; Sea C. Min; Sanghee Han; Seok-Geun Lee; Jun Tae Kim (Food Chemistry, 2026)

Aboveground living plant-based methane production does not dominate methane emissions in terrestrial ecosystems - Zhi-Ping Wang; Luke C. Jeffrey; Josep Barba; Katerina Machacova; Xi-Mei Zhang; Ang Li; Shi-Jie Han (Planta, 2026)

miR-495-3p Attenuates Neuronal Apoptosis Through The Activation of Wnt/MAPK Pathways in Ischemic Stroke - Eunjae Jang; Hee Yu; Jiyun Choi; Jin Yoo; Hyong-Ho Cho; Byeong C. Kim; Han-Seong Jeong; Sujeong Jang (Molecular Neurobiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Enhancing carbon storage through proactively managing fire-prone coniferous mountain forests - Weichao Guo; Mohammad Safeeq; Guotao Cui; Philip C. Myint; Panmei Jiang; Han Guo; Michael L. Goulden; Kristen D. Emmett; Stephen C. Hart; Roger C. Bales (Ecological Modelling, 2025)

A full sub-2 nm and acid-resistant MOF-COF ionic diode membrane for efficient ionic gradient power generation - Norman C.-R. Chen; Po-Chun Han; Li-Hsien Yeh; Yu-Hsiang Peng; Chia-An Lung; Yusuke Yamauchi; Kevin C.-W. Wu (Chemical Engineering Journal, 2025)

Zircon U-Pb Ages and Sr-Nd-Hf Isotopes Geochemistry of I-Type Granites in the Jiangda-Weixi Region, Eastern Tibet: Implications for the Tectonic Evolution of the Paleo-Tethyan Orogen - Rui Gao; Tao Wu; Andrew C. Kerr; Han Liu; Long Xiao; Wan Huang (Journal of Earth Science, 2025)

Mineral heterogeneity dominates the tensile failure mode of Eastern Himalayan Gneiss - Shijie Liu; Hengxing Lan; C. Derek Martin; Langping Li; Han Bao (Journal of Structural Geology, 2025)

Quantification of geothermal carbon dioxide fluxes using radiocarbon - Jocelyn C. Turnbull; Tsung-Han Jimmy Yang; Agnes Mazot; Mus Hertoghs; Isabelle Chambefort (Chemical Geology, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Investigation of bacterial communities and antibiotic-resistant bacteria in the aquatic environments from Kathmandu, Nepal - Santosh Khanal; Sudeep K C; Tista Prasai Joshi; Ziming Han; Yu Zhang; Min Yang; Dev Raj Joshi (Journal of Environmental Chemical Engineering, 2025)

Reaction calorimetry and structural crystal properties of non-ideal binary rhabdophane solid solutions (Ce1−xREExPO4·nH2O) - Alexander P. Gysi; Nicole C. Hurtig; Hannah Juan Han; Emma C. Kindall; Xiaofeng Guo; Dmitrii A. Kulik; George Dan Miron (Geochimica et Cosmochimica Acta, 2025)

Agaricus bisporus mushrooms are supplied with water through both apoplastic as well as symplastic routes from distinct substrate layers - Koen C. Herman; Guus van Iersel; Jan Dijksterhuis; Han A.B. Wösten; Robert-Jan Bleichrodt (Fungal Biology, 2025)

Efficient adsorption of phosphate on magnetic Fe3O4@MOF@LDH superstructures: Kinetics, thermodynamics, and mechanisms - Zhang Liu; Wei Han; C. Marquina; Joseph K.C. Kwan; M. Ricardo Ibarra; King Lun Yeung (Environmental Research, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Extension of lifespan by epicatechin, halofuginone and mitoglitazone in male but not female genetically heterogeneous mice - Randy Strong; James F. Nelson; Molly A. Bogue; Jerry R. Colca; Martin Denzel; Vivian Diaz; Brian N. Finck; Vadim N. Gladyshev; Steve Horvath; Nisi Jiang; Tracy Keller; Rolf F. Kletzien; et al. (GeroScience, 2025)
Mice bred in 2021 were tested by the Interventions Testing Program (ITP) for possible lifespan benefits of 2BAct (2BA), dichloroacetate (DCA), Epicatechin (EPI), Forskolin (FSK), Halofuginone (HAL) and Mitoglitazone (MIT). All agents were administered in the diet ad libitum beginning at 7 months of age. In male mice, EPI increased median lifespan by ~ 5%, and HAL and MIT each increased median lifespan by ~ 9%. EPI and HAL, but not MIT, increased 90% survival. In addition to adding 3 new agents to the list of interventions identified by the ITP that extend lifespan, this report continues the strong male bias in the efficacy of life-extending drugs identified so far.

P31-21 Detection Methods for Injection-Induced Pseudoallergic Reactions - C. Liu; Y. Yi; C. Li; Y. Zhao; Y. Zhang; J. Han; J. Tian; C. Pan; L. Wang; S. Liu; L. Ma; A. Liang (Toxicology Letters, 2025)

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Surface functionalized polystyrene nanoplastics impair nutrient assimilation from corn kernels (Zea mays L.) in a simulated human digestive tract - Chunyang Li; Heping Shang; Xiaoyan Hu; Ian Eggleston; David Julian McClements; Bin Han; Jason C. White; Chuanxin Ma; Baoshan Xing (Journal of Hazardous Materials, 2025)

Novel miRNAs, miR-937-3p, miR-4536-3p, and miR-4650-5p, can Modulate Neuronal Differentiation via the Wnt/MAPK Pathway in SH-SY5Y Cells - Jiyun Choi; Eunjae Jang; Haewon Jeong; Jinsu Hwang; Hyong-Ho Cho; Byeong C. Kim; Geupil Jang; Han-Seong Jeong; Sujeong Jang (Molecular Neurobiology, 2025)

Seismic observations from injection experiments and a recharge event in a karst aquifer: potential compressed air pocket release - Andrew J. Luhmann; Susan L. Bilek; Matthew D. Covington; Ronni Grapenthin; Han Byul Woo; Jacob Alexander Gochenour; E. Calvin Alexander; Scott C. Alexander; Martin R. Larsen (Hydrogeology Journal, 2025)
After deploying a seismic network above a karst aquifer that feeds Bear Spring in Minnesota, USA, three injection experiments were conducted, which involved pouring ~10,000 L of water just above an overflow spring to induce and characterize ambient seismic noise from subsurface water flow. A rainstorm event followed the second experiment and caused the overflow spring to start flowing with meters of water level rise, increasing the total spring discharge (perennial and overflow emanations) from ~100 to 300 L/s. Water level, electrical conductivity, and temperature data were used to estimate the conduit hydraulic diameter of ~0.06 m from the second injection experiment and ~0.5 m from the recharge event, which suggested both open channel and full pipe conduit flow. The rainstorm led to the largest seismic signals over a 5 s period while water levels rose, producing ground motion up to ~0.5 mm/s, possible oscillatory behavior, and 1–150 J of radiated seismic energy at frequencies of ~30–50 and 70–90 Hz (similar to signal frequencies when the large water slug from the second injection experiment reached a sump or water-filled passage). The seismic sources originated from multiple directions. The calculations suggest these signals came from conduits with air pockets that were compressed from rising water levels and later released via ventilation pathways. Seismic records of this process enable identification of the change in mode of water level propagation and potential delineation of unknown subsurface pathways, facilitating karst aquifer characterization beyond what is possible with traditional monitoring strategies.

Characterization of pure mycelium materials from different mushroom-forming fungi - Jeroen G. van den Brandhof; Noortje Hansen; Chen Hou; Sander C. Broers; Martin Tegelaar; Han A. B. Wösten (Antonie van Leeuwenhoek, 2025)
Pure mycelium materials (PMMs) are a sustainable alternative for a range of non-sustainable products such as textile, leather and meat. So far, properties of PMMs of different fungi have not been systematically assessed. Here, 11 mushroom-forming fungi, of which 10 isolated from nature, were grown in liquid shaken cultures. Schizophyllum commune, Ganoderma resinaceum , and Trametes betulina produced the highest biomass (8.62, 7.58, and 6.94 g L −1 , respectively) when grown as mono-cultures in malt extract broth. Therefore, PMM properties were determined of mono-cultures, mixed-cultures, and co-cultures of these three fungi. The maximum tensile strength of the PMMs of the mono-cultures, mixed-cultures, and co-cultures of S. commune , G. resinaceum , and T. betulina did not show significant differences and ranged between 4.5 to 6.3 MPa. The elongation at break of the different PMMs was generally low and ranged between 0.8 and 1.6%. The Young’s modulus of the PMMs also showed relatively small differences ranging between 408 and 710 MPa. The G. resinaceum PMMs showed the lowest water uptake, while the S. commune mono-, mixed- and co-culture PMMs showed the highest water contact angle. Together, it is concluded that the properties of the mono-, mixed-, and co-cultures of S. commune , G. resinaceum , and T. betulina are not very different. These data suggest that the species of mushroom forming fungi does not have a major impact on PMM properties of biomass from liquid shaken cultures.

Arbuscular mycorrhizal fungi suffer from perfluorooctanoic acid in soil but ameliorate negative effects on plant performance - Han Yan; Tingting Zhao; Baile Xu; Anika Lehmann; Matthias C. Rillig (Applied Soil Ecology, 2025)

A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

Single-Session Feasibility of Cough Skill Training in Cerebellar Ataxia - James C. Borders; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2025)

Blood Cells as a Cellular Biomarker for Mitochondrial Function in a Experimental Model of Acute Carbon Monoxide Poisoning with Treatment - Devesh Bungatavula; John C. Greenwood; Frances S. Shofer; Guthrie Buehler; Shih-Han Kao; Matthew Kelly; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2025)
Introduction Carbon monoxide (CO) is a leading cause of environmental poisoning in the United States with substantial mortality and morbidity. The mechanism of CO poisoning is complex and includes hypoxia, inflammation, and mitochondrial dysfunction. Currently both biomarkers and therapies for CO poisoning are limited and require new approaches. Methods Rats (~ 300 g) were divided into four groups of ten rodents per group (exposure): Control (room air), CO-400 (400 ppm), CO-1000 (1000 ppm) and CO-2000 (2000 ppm). Rodents received the assigned exposure through a secured tracheotomy tube over 120 min followed by 30 min of re-oxygenation at room air for a total of 150 min. Five additional rodents in each group were administered a succinate prodrug (NV354) at the start of exposure for the duration of the experiment until the reoxygenation period as separate experiments. Cortical brain tissue and whole blood were obtained for mitochondrial respiration. Stored plasma and snap frozen tissue stored at -80 o C were used to obtain protein quantification with Western Blotting. Results All animals in the Sham, CO-400, and CO-1000 groups survived until the end of the exposure period; no animals in the CO-2000 groups survived the exposure and were counted as attrition. We observed a dose-dependent decrease in key respiratory states in both isolated brain mitochondria and peripheral blood mononuclear cells (PBMCs), and, PBMCs respiration more positively correlated with isolated brain mitochondria when compared to carboxyhemoglobin (COHb). There was no significant difference in mitochondrial respiratory states in animals treated with NV354 compared to the untreated group. Conclusions The primary findings from this study include: (1) A dose-dependent decrease with key respiration states with higher concentrations of CO; (2) PBMCs had a higher correlation to isolated brain mitochondria respiration when compared to COHb; and (3) there was no treatment effect with the use of NV354.

Sedimentary conditions and palaeoenvironment during the Early Cretaceous: Evidence from macerals and organic carbon isotopes of the coal from Hailar Basin, Northeast China - Rongkun Jia; Jingjing Liu; James C. Hower; Yaofa Jiang; Shumao Zhao; Qiuchan Han; Niande Shang; Jiawei Feng; Kaiyan Teng (Cretaceous Research, 2025)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

Synthesis of Population Trends Reveals Seascape‐Wide Reorganisation of Biodiversity From Microalgae to Birds - Anika Happe; Kasper J. Meijer; Jan‐Claas Dajka; Oscar Franken; Holger Haslob; Laura L. Govers; Michael Kleyer; Annebelle C. M. Kok; Lucie Kuczynski; Kertu Lõhmus; Sancia E. T. van der Meij; Han Olff; et al. (Global Change Biology, 2025)
Many monitoring programs aim to understand regional biodiversity patterns in relation to global and regional conservation targets, using either community‐wide biodiversity metrics to describe the community status or trends of pre‐selected “key” species as biodiversity change indicators. However, the former often lacks information on which species are changing, and the latter is heavily skewed towards specific taxa, potentially overlooking changes in other, functionally important taxa. We gathered an extensive set of monitoring data with over 3000 population trends (ranging from 5 to 91 years in duration) for a wide range of taxa across the Wadden Sea. We combined a systematic and quantitative categorization of population trends (weighted vote count) with a meta‐analysis on different taxonomic levels. This allowed the first cross‐taxa synopsis of species declines and increases and determined their directionalities throughout time. Our meta‐analysis showed an overall decrease in population size for fish, zooplankton, and plant species, while birds showed an overall increase. However, these increases mask recent negative trends within specific bird groups since the late 1990s. In contrast, fish populations exhibited declines over the entire monitoring period. Species with declining populations (losers) were phylogenetically related, whereas species with increasing populations (winners) represented various organismal groups. Directionality and onsets of change in population trends were temporally synchronized throughout several groups, such as bivalves, fish, and birds, and may provide warning signals for future local extinctions in these taxa. Our analysis moves beyond typical indicator species by including the entire species inventory of the system. Basal trophic levels of aquatic ecosystems, such as zooplankton and phytoplankton, are often missing from policy assessments but are among the most important organism groups for ecosystem functioning. Here, we show that without additional monitoring effort, a systematic analysis of population trends adds to our understanding of trophic and compositional restructuring of ecosystems.

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comprehensive wheat lodging detection under different UAV heights using machine/deep learning models - Jianing Long; Zhao Zhang; Qu Zhang; Xiaohui Zhao; C. Igathinathane; Jianfei Xing; Chayan Kumer Saha; Wenyi Sheng; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2025)

Phosphorus-to-calcium ratios in benthic foraminiferal shells as a proxy for coastal seawater phosphate concentrations - Han Zhang; Bochao Xu; Zhiqing Lai; Adina Paytan; William C. Burnett; Xiaoyi Guo; Lihui Ren; Yuan Lu; Jianing Zhang; Huamao Yuan; Qingzhen Yao; Zhigang Yu (Earth and Planetary Science Letters, 2025)

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

Polylactic acid microplastics induced negative priming and improved carbon sequestration via microbial processes in different paddy soils - Liying Chen; Lanfang Han; Fayuan Wang; Qi'ang Chen; Hongkai Huang; Jie Wang; Chuanxin Ma; Ke Sun; Matthias C. Rillig; Yakov Kuzyakov; Zhifeng Yang (Soil Biology and Biochemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Curcumin Improves Hippocampal Cell Bioenergetics, Redox and Inflammatory Markers, and Synaptic Proteins, Regulating Mitochondrial Calcium Homeostasis - Claudia Jara; Angie K. Torres; Han S. Park-Kang; Lisette Sandoval; Claudio Retamal; Alfonso Gonzalez; Micaela Ricca; Sebastián Valenzuela; Michael P. Murphy; Nibaldo C. Inestrosa; Cheril Tapia-Rojas (Neurotoxicity Research, 2025)

Adsorption of cadmium ion from water by using non-toxic iron oxide adsorbent; experimental and statistical modelling analysis - D. Gusain; S. Sahani; Y. C. Sharma; S. S. Han (International Journal of Environmental Science and Technology, 2025)

Grazing intensity by sheep affects spatial diversity in botanical composition of Inner Mongolian grassland - Xu Han; Raúl Ochoa-Hueso; Yong Ding; Xiliang Li; Ke Jin; Wim H. van der Putten; Paul C. Struik (Agriculture, Ecosystems & Environment, 2025)

Zoonotic Host Richness in the Global Wildland–Urban Interface - Rohan D. Simkin; Barbara A. Han; Volker C. Radeloff; Shannon LaDeau; Franz Schug; Karen C. Seto (Global Change Biology, 2025)
Where human settlements abut or intermix with wildlands, people may encounter animals that host zoonotic pathogens which can spillover to cause human disease. Known as the wildland–urban interface (WUI), this zone occupies around 5% of the Earth's surface and is home to 3.5 billion people. The rapid spread of SARS‐CoV‐2 has demonstrated the importance of understanding risk factors for disease among an increasingly urbanized population. However, the contribution of the WUI to zoonotic disease risk is poorly understood. Here, we show that low‐level host richness occurs throughout most of the global WUI, and 20% of the human WUI population live in zones of particularly high zoonotic potential, where more than 20 host species could occur. Zones of high zoonotic potential are concentrated in low–middle‐income countries (LMICs) across equatorial Africa, Brazil, Central America, and Southeast Asia where vulnerability is further elevated by widespread poverty, inadequate housing, and lack of easily accessible healthcare. Three of four people living in WUIs with high host richness (520 million people) are in LMICs. Of this population, 35% (183 million) live in and around cities in West, East, and South Africa. This means that WUI‐based populations of LMICs may face the double threat of high zoonotic potential and vulnerability to disease. Our results identify global priorities for monitoring exposure to zoonotic diseases in the rapidly expanding WUI.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Saltiness perception in gel-based food systems (gels and emulsion-filled gels) - Essam Hebishy; Han Du; Thais C. Brito-Oliveira; Samantha C. Pinho; Song Miao (Critical Reviews in Food Science and Nutrition, 2025)

Purinergic signaling by TCRαβ+ double-negative T regulatory cells ameliorates liver ischemia–reperfusion injury - Hua Jin; Mingyang Li; Xiyu Wang; Lu Yang; Xinjie Zhong; Zihan Zhang; Xiaotong Han; Jingjing Zhu; Mengyi Li; Songlin Wang; Simon C. Robson; Guangyong Sun; et al. (Science Bulletin, 2025)

Development of Zinc-Containing Chitosan/Gelatin Coatings with Immunomodulatory Effect for Soft Tissue Sealing around Dental Implants - Jing Han; Jorine G. F. Sanders; Lea Andrée; Bart A. J. A. van Oirschot; Adelina S. Plachokova; Jeroen J. J. P. van den Beucken; Sander C. G. Leeuwenburgh; Fang Yang (Tissue Engineering and Regenerative Medicine, 2025)
BACKGROUND: Soft tissue integration (STI) around dental implant abutments is a prerequisite to prevent bacterial invasion and achieve successful dental implant rehabilitation. However, peri-implant STI is a major challenge after dental abutment placement due to alterations in the immune microenvironment upon surgical dental implant installation. METHODS: Based on known immunomodulatory effects of zinc, we herein deposited zinc/chitosan/gelatin (Zn/CS/Gel) coatings onto titanium substrates to study their effect on macrophages. First, we exposed macrophages to cell culture media containing different zinc ion (Zn 2+ ) concentrations. Next, we explored the immunomodulatory effect of Zn/CS/Gel coatings prepared via facile electrophoretic deposition (EPD). RESULTS: We found that Zn 2+ effectively altered the secretome by reducing the secretion of pro-inflammatory and enhancing pro-regenerative cytokine secretion, particularly at a Zn 2+ supplementation of approximately 37.5 μM. Zn/CS/Gel coatings released Zn 2+ in a concentration range which effectively stimulated pro-regenerative macrophage polarization as demonstrated by M2 macrophage polarization. Additionally, the impact of these Zn 2+ -exposed macrophages on gingival fibroblasts incubated in conditioned medium showed stimulated adhesion, proliferation, and collagen secretion. CONCLUSION: Our promising results suggest that controlled release of Zn 2+ from Zn/CS/Gel coatings could be applied to immunomodulate peri-implant STI, and to enhance dental implant survival.

Energy burden and mental health: A national study in the United States - Soojin Han; Ming Hu; Xue Gao; Youqin Huang; Fei Guo; Gordon C. Shen; Donggen Wang; Shao Lin; Kai Zhang (Science of The Total Environment, 2024)

The fungal strain promotes rapid agarwood resin production with medicinally accepted agarotetrol level - Tian-Ye Du; Saowaluck Tibpromma; Kevin D. Hyde; Yue-Hu Wang; Putarak Chomnunti; Ekachai Chukeatirote; Wen-Hua Lu; Ausana Mapook; Dong-Qin Dai; Douglas S.A. Wijesundara; Abdallah M. Elgorban; Nakarin Suwannarach; et al. (Food Bioscience, 2024)

Kidney tissue loading reduces the critical cooling/warming rates of cryoprotective solutions - Zonghu Han; Lakshya Gangwar; Bat-Erdene Namsrai; Joseph S. Rao; Michael L. Etheridge; Jeunghwan Choi; Erik B. Finger; John C. Bischof (Cryobiology, 2024)

Kidney tissue loading reduces the critical cooling and warming rates of VS55 and VMP cryoprotective solutions - Zonghu Han; Lakshya Gangwar; Bat-Erdene Namsrai; Joseph Sushil Rao; Cameron Scheithauer; Michael L. Etheridge; Erik B. Finger; John C. Bischof; Jeunghwan Choi (Cryobiology, 2024)

VOC emission rates from an indoor surface using a flux chamber and PTR-MS - Han N. Huynh; Jenna C. Ditto; Jie Yu; Michael F. Link; Dustin Poppendieck; Delphine K. Farmer; Marina E. Vance; Jonathan P.D. Abbatt (Atmospheric Environment, 2024)

Correction: A Fresh Take: Seasonal Changes in Terrestrial Freshwater Inputs Impact Salt Marsh Hydrology and Vegetation Dynamics - Maya S. Montalvo; Emilio Grande; Anna E. Braswell; Ate Visser; Bhavna Arora; Erin C. Seybold; Corianne Tatariw; John C. Haskins; Charlie A. Endris; Fuller Gerbl; Mong-Han Huang; Darya Morozov; et al. (Estuaries and Coasts, 2024)

A Fresh Take: Seasonal Changes in Terrestrial Freshwater Inputs Impact Salt Marsh Hydrology and Vegetation Dynamics - Maya S. Montalvo; Emilio Grande; Anna E. Braswell; Ate Visser; Bhavna Arora; Erin C. Seybold; Corianne Tatariw; John C. Haskins; Charlie A. Endris; Fuller Gerbl; Mong-Han Huang; Darya Morozov; et al. (Estuaries and Coasts, 2024)
Salt marshes exist at the terrestrial-marine interface, providing important ecosystem services such as nutrient cycling and carbon sequestration. Tidal inputs play a dominant role in salt marsh porewater mixing, and terrestrially derived freshwater inputs are increasingly recognized as important sources of water and solutes to intertidal wetlands. However, there remains a critical gap in understanding the role of freshwater inputs on salt marsh hydrology, and how this may impact marsh subsurface salinity and plant productivity. Here, we address this knowledge gap by examining the hydrologic behavior, porewater salinity, and pickleweed ( Sarcocornia pacifica also known as Salicornia pacifica) plant productivity along a salt marsh transect in an estuary along the central coast of California. Through the installation of a suite of hydrometric sensors and routine porewater sampling and vegetation surveys, we sought to understand how seasonal changes in terrestrial freshwater inputs impact salt marsh ecohydrologic processes. We found that salt marsh porewater salinity, shallow subsurface saturation, and pickleweed productivity are closely coupled with elevated upland water level during the winter and spring, and more influenced by tidal inputs during the summer and fall. This seasonal response indicates a switch in salt marsh hydrologic connectivity with the terrestrial upland that impacts ecosystem functioning. Through elucidating the interannual impacts of drought on salt marsh hydrology, we found that the severity of drought and historical precipitation can impact contemporary hydrologic behavior and the duration and timing of the upland-marsh hydrologic connectivity. This implies that the sensitivity of salt marshes to climate change involves a complex interaction between sea level rise and freshwater inputs that vary at seasonal to interannual timescales.

In-field grading and sorting technology of apples: A state-of-the-art review - Jiangfan Yu; Zhao Zhang; Yifei Li; Wanjia Hua; Xinyu Wei; C. Igathinathane; Mustafa Mhamed; Wenqiang Zhang; Xiaoqiang Jiao; Liling Yang; Man Zhang; Han Li (Computers and Electronics in Agriculture, 2024)

Exploring synthesis techniques for an imidazole-based one-component epoxy latent curing agent: Chemical capping and mechano-chemical capsuling - Han Gyeol Jang; Deok Jae Lim; Sohyun An; Jong Hyuk Park; Min Park; Jinwoo Park; Hyungbum Park; Byeong-Su Kim; Doh C. Lee; Jaewoo Kim (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

“Spicy Touch”: Cross-modal associations between hand-feel touch and capsaicin-induced oral irritation - Ragita C. Pramudya; Dipankar Choudhury; Min Zou; Han-Seok Seo (Food Research International, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Seasonally Changing Interactions of Species Traits of Termites and Trees Promote Complementarity in Coarse Wood Decomposition - Chao Guo; Bin Tuo; Sebastian Seibold; Hang Ci; Bi‐Le Sai; Han‐Tang Qin; En‐Rong Yan; Johannes H. C. Cornelissen (Ecology Letters, 2024)
Complementary resource use by functionally different species may accelerate ecosystem processes. However, how co‐variation in plant traits and animal traits promotes complementarity through temporal plant–animal interactions is poorly understood, even less so in detrital systems, thereby hampering our fundamental understanding of decomposition and carbon turnover. We hypothesised that, in seasonal subtropical forests where termites are major deadwood decomposers, trait complementarity of both termite species and tree species should promote overall deadwood decomposition through different seasons and years. Findings from a four‐year coarse wood decomposition experiment involving 27 tree and 5 termite species support this hypothesis. Phenological and mandibular traits of the two most abundant termite species controlled wood decomposition of tree species differing in wood traits, through the seasons over 4 years, thereby promoting overall deadwood decomposition rates. Our findings indicate that complementarity in functional trait co‐variation in plants and animals plays an important role in carbon cycling.

Cytotoxicity and cell membrane interactions of choline-based ionic liquids: Comparing amino acids, acetate, and geranate anions - Mohamad El Mohamad; Qi Han; Brendan Dyett; Haitao Yu; Sara Edgecomb; Mercedes C. Pride; Claylee M. Chism; Angela Roberts; Deauntaye Jones; Eden E.L. Tanner; Calum J. Drummond; Tamar L. Greaves; et al. (Chemosphere, 2024)

P08-05 The Role and mechanism of O-GlcNAcylation in abnormalities of oocyte maturation and early embryonic development caused by PFOS exposure - Z. Wu; Q. Yuan; H. Qian; S. Han; Q. Xu; Y. Xia; Y. Fan; C. Lu (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Proxies of hypoxia and submarine groundwater discharge in the coastal ocean: Foraminiferal shell chemical perspectives - Xiaoyi Guo; Ergang Lian; Huamao Yuan; William C. Burnett; Han Zhang; Miaomiao Zhang; Kai Xiao; Qinsheng Wei; Zhigang Yu; Bochao Xu (Marine Chemistry, 2024)

β-adrenergic stimulation after rewarming does not mitigate hypothermia-induced contractile dysfunction in rat cardiomyocytes - Torstein Schanche; Young Soo Han; Cole W. Jensen; Grace M. Arteaga; Torkjel Tveita; Gary C. Sieck (Cryobiology, 2024)

BML-281 promotes neuronal differentiation by modulating Wnt/Ca2+ and Wnt/PCP signaling pathway - Jiyun Choi; Seoyeon Gang; Mahesh Ramalingam; Jinsu Hwang; Haewon Jeong; Jin Yoo; Hyong-Ho Cho; Byeong C. Kim; Geupil Jang; Han-Seong Jeong; Sujeong Jang (Molecular and Cellular Biochemistry, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Life cycle environmental hotspots analysis of typical electrochemical, mechanical and electrical energy storage technologies for different application scenarios: Case study in China - Yanxin Li; Xiaoqu Han; Lu Nie; Yelin Deng; Junjie Yan; Tryfon C. Roumpedakis; Dimitrios-Sotirios Kourkoumpas; Sotirios Karellas (Journal of Cleaner Production, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Sustainable regulation of calcium magnesium phosphate and rapeseed cake on soil-tea system in Mount Lushan, China - C. Han; Y. Ding; Z. J. Tang; Y. Q. Lai; M. Liu (Environmental Geochemistry and Health, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Human atherosclerotic plaque transcriptomics reveals endothelial beta-2 spectrin as a potential regulator a leaky plaque microvasculature phenotype - Timo Rademakers; Marco Manca; Han Jin; Tanguy Orban; Ljubica Matic Perisic; Hubertus J. M. Frissen; Frank Rühle; Petra Hautvast; Jos van Rijssel; Kim van Kuijk; Barend M. E. Mees; Carine J. Peutz-Kootstra; et al. (Angiogenesis, 2024)
The presence of atherosclerotic plaque vessels is a critical factor in plaque destabilization. This may be attributable to the leaky phenotype of these microvessels, although direct proof for this notion is lacking. In this study, we investigated molecular and cellular patterns of stable and hemorrhaged human plaque to identify novel drivers of intraplaque vessel dysfunction. From transcriptome data of a human atherosclerotic lesion cohort, we reconstructed a co-expression network, identifying a gene module strongly and selectively correlated with both plaque microvascular density and inflammation. Spectrin Beta Non-Erythrocytic 1 ( sptbn1 ) was identified as one of the central hubs of this module (along with zeb1 and dock1 ) and was selected for further study based on its predominant endothelial expression. Silencing of sptbn1 enhanced leukocyte transmigration and vascular permeability in vitro, characterized by an increased number of focal adhesions and reduced junctional VE-cadherin. In vivo, sptbn1 knockdown in zebrafish impaired the development of the caudal vein plexus. Mechanistically, increased substrate stiffness was associated with sptbn1 downregulation in endothelial cells in vitro and in human vessels. Plaque SPTBN1 mRNA and protein expression were found to correlate with an enhanced presence of intraplaque hemorrhage and future cardiovascular disease (CVD) events during follow-up. In conclusion, we identify SPTBN1 as a central hub gene in a gene program correlating with plaque vascularisation. SPTBN1 was regulated by substrate stiffness in vitro while silencing blocked vascular development in vivo, and compromised barrier function in vitro. Together, SPTBN1 is identified as a new potential regulator of the leaky phenotype of atherosclerotic plaque microvessels.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Molecular phylogeny and morphology reveal two new species of Conocybe (Bolbitiaceae, Agaricales) from southwest China - Wenhua Lu; Nakarin Suwannarach; Saisamorn Lumyong; Abdallah M. Elgorban; Dong-Qin Dai; Arun K. Dutta; Li-Hong Han; Saowaluck Tibpromma; Samantha C. Karunarathna (New Zealand Journal of Botany, 2024)

Extended-spectrum β-lactamase-producing bacteria and their resistance determinants in different wastewaters and rivers in Nepal - Santosh Khanal; Sudeep K C; Tista Prasai Joshi; Ziming Han; Chunzhen Wang; Jyoti Maharjan; Reshma Tuladhar; Dev Raj Joshi (Journal of Hazardous Materials, 2024)

Changes in water conservation and possible causes in the Yellow River Basin of China during the recent four decades - Guo Chen; Depeng Zuo; Zongxue Xu; Guoqing Wang; Yuna Han; Dingzhi Peng; Bo Pang; Karim C. Abbaspour; Hong Yang (Journal of Hydrology, 2024)

Field demonstration of a 10 MW CO2 capture pilot plant in extended operation using KoSol absorbents for treating off-gas in a coal fired power plant - No-Sang Kwak; Jinkyu Jung; Junghyun Lee; Sung-Chul Han; Jae-Goo Shim; Kyung-Min Kim; Doh C. Lee (International Journal of Greenhouse Gas Control, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Psychosocial barriers and facilitators for cascade genetic testing in hereditary breast and ovarian cancer: a scoping review - Agani Afaya; Sung-Won Kim; Hyung Seok Park; Myong Cheol Lim; Mi Sook Jung; Eun Ji Nam; Ji Soo Park; Joon Jeong; Jai Min Ryu; JiSun Kim; Jihye Kim; Minkyoung Kim; et al. (Familial Cancer, 2024)

Macroalgal eukaryotic microbiome composition indicates novel phylogenetic diversity and broad host spectrum of oomycete pathogens - Natalia Timanikova; Kyle Fletcher; Jon‐Wong Han; Pieter van West; Steve Woodward; Gwang‐Hoon Kim; Frithjof C. Küpper; Marius Wenzel (Environmental Microbiology, 2024)
Seaweeds are important components of marine ecosystems with emerging potential in aquaculture and as sources of biofuel, food products and pharmacological compounds. However, an increasingly recognised threat to natural and industrial seaweed populations is infection with parasitic single‐celled eukaryotes from the relatively understudied oomycete lineage. Here we examine the eukaryomes of diverse brown, red and green marine macroalgae collected from polar (Baffin Island), cold‐temperate (Falkland Islands) and tropical (Ascension Island) locations, with a focus on oomycete and closely related diatom taxa. Using 18S rRNA gene amplicon sequencing, we show unexpected genetic and taxonomic diversity of the eukaryomes, a strong broad‐brush association between eukaryome composition and geographic location, and some evidence of association between eukaryome structure and macroalgal phylogenetic relationships (phylosymbiosis). However, the oomycete fraction of the eukaryome showed disparate patterns of diversity and structure, highlighting much weaker association with geography and no evidence of phylosymbiosis. We present several novel haplotypes of the most common oomycete Eurychasma dicksonii and report for the first time a cosmopolitan distribution and absence of host specificity of this important pathogen. This indicates rich diversity in macroalgal oomycete pathogens and highlights that these pathogens may be generalist and highly adaptable to diverse environmental conditions.

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Seeding detection and distribution evaluation using the developed automatic maize seeding machine - Yunxia Li; Zhao Zhang; Afshin Azizi; Muhammad Hilal Kabir; C. Igathinathane; Xiqing Wang; Muhammad Naveed Tahir; Xiongzhe Han; Man Zhang (Computers and Electronics in Agriculture, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Floral resource partitioning of coexisting bumble bees: Distinguishing species‐, colony‐, and individual‐level effects - Zhong‐Ming Ye; Yong‐Deng He; Pedro J. Bergamo; Michael C. Orr; Wen Huang; Xiao‐Fang Jin; Han‐Ning Lun; Qing‐Feng Wang; Chun‐Feng Yang (Ecology, 2024)
Resource partitioning is considered a key factor in alleviating competitive interactions, enabling coexistence among consumer species. However, most studies have focused on resource partitioning between species, ignoring the potentially critical role of intraspecific variation in resource use. We investigated floral resource partitioning across species, colonies, and individuals in a species‐rich bumblebee community in the diversification center of bumblebees. We used a total of 10,598 bumblebees belonging to 13 species across 5 years in the Hengduan Mountains of southwest China. First, we evaluated the influence of a comprehensive set of floral traits, including both those related to attractiveness (flower color and shape) and rewards (pollen, sugar ratio, nectar volume, sugar concentration, and amino acid content) on resource partitioning at the species level in bumblebee–plant networks. Then, we explored intraspecific resource partitioning on the colony and individual levels. Our results suggest that bumblebee species differ substantially in their use of the available floral resources, and that this mainly depends on flower attractiveness (floral color and shape). Interestingly, we also detected floral resource partitioning at the colony level within all commonest bumblebee species evaluated. In general, floral resource partitioning between bumblebee individuals decreased with species‐ and individual‐level variation in body size (intertegular span). These results suggest that bumblebee species may coexist via the flexibility in their preferences for specific floral traits, which filters up to support the co‐occurrence of high numbers of species and individuals in this global hotspot of species richness.

Mutual facilitation between foundation species Mytilus edulis and Lanice conchilega promotes habitat heterogeneity on tidal flats - Janne Nauta; Kasper J. Meijer; Lissie W. de Groot; Valérie C. Reijers; Tjeerd J. Bouma; Daphne van der Wal; Han Olff; Sander J. Holthuijsen; Allert I. Bijleveld; Henk W. van der Veer; Oscar Franken; Laura L. Govers (Frontiers in Marine Science, 2024)
Foundation species that modify their habitat can facilitate other species, including other foundation species. Most studies focus solely on a single foundation species, overlooking such facilitation cascades. In this study, we investigated the interactions between the two coastal foundation species Mytilus edulis (blue mussel) and Lanice conchilega (sand mason worm). We investigated whether these species engage in facilitative interactions or if their association simply reflects a shared ecological niche on the soft-sediment intertidal flats of the Dutch Wadden Sea. To do so, we performed species distribution modeling, manipulative field experiments, and field surveys. We found a positive association between both foundation species, with a 2.45 times higher occurrence of both species compared to a random distribution. In addition, these species partially occupied the same ecological niche. We demonstrated that L. conchilega provided settlement substrate for M. edulis spat, increasing densities by 400 times compared to bare plots. Furthermore, M. edulis reefs facilitated L. conchilega occurrence in the wake of the reef. Biogenic reef development revealed that this interspecific facilitation resulted in spatial habitat heterogeneity. Therefore, we conclude that interspecific facilitation can significantly enhance the occurrence of these two important intertidal foundation species. Acknowledgment of such complex facilitation interactions has an untapped potential for improving the success of restoration and conservation programs.

Soil pH drives the relationship between the vertical distribution of soil microbial biomass and soil organic carbon across terrestrial ecosystems: A global synthesis - Yun Liang; Matthias C. Rillig; Han Y.H. Chen; Rongxu Shan; Zilong Ma (CATENA, 2024)

Hazard and risk characterization of 56 structurally diverse PFAS using a targeted battery of broad coverage assays using six human cell types - Lucie C. Ford; Hsing-Chieh Lin; Han-Hsuan D. Tsai; Yi-Hui Zhou; Fred A. Wright; Alexander Sedykh; Ruchir R. Shah; Weihsueh A. Chiu; Ivan Rusyn (Toxicology, 2024)

Development and validation of an in situ high-resolution technique for measuring antibiotics in sediments - Yanying Li; Qiuyu Rong; Chao Han; Hanbing Li; Jun Luo; Liying Yan; Degao Wang; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

Flexural behavior of GFRP-RC beams confined with CFRP in compression zone - Hongwei Wang; Jinjin Xu; Xu Jiang; Xiaoyan Han; Kaiming Pan; Rena C. Yu; Zhimin Wu (Engineering Structures, 2024)

Photocatalytic hydrogen production from seawater splitting: Current status, challenges, strategies and prospective applications - Van-Han Dang; Tuan-Anh Nguyen; Minh-Vien Le; Dinh Quan Nguyen; Yen Han Wang; Jeffery C.-S. Wu (Chemical Engineering Journal, 2024)

Fire activities and their impacts on local ecosystems in the southern Ordos Basin during the Middle Jurassic: Evidence from pyrogenic PAHs and petrography of inertinite-rich coal - Qiuchan Han; Jingjing Liu; James C. Hower; Tim A. Moore; Niande Shang; Shumao Zhao; Rongkun Jia; Shifeng Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Indoor particulate matter concentrations and air cleaner intervention association with biomarkers in former smokers with COPD - Ashraf Fawzy; Han Woo; Sarath Raju; Daniel C. Belz; Nirupama Putcha; Marlene S. Williams; Meredith C. McCormack; Kirsten Kohler; Nadia N. Hansel (Environmental Research, 2024)

Effectiveness and potential mechanism of hydrothermal modification of attapulgite for cadmium passivation in soil - G. Ma; J. Ren; L. Tao; X. Han; C. Liao; Y. Zhou; J. Ding; Y. Zhou; K. Bi (International Journal of Environmental Science and Technology, 2024)

Graphical Discrimination of New Zealand Honey from International Honey Using Elemental Analysis - Megan N. C. Grainger; Hannah Klaus; Nyssa Hewitt; Han Gan; Amanda D. French (Biological Trace Element Research, 2024)
This study investigated the potential of utilising the elemental fingerprinting of honey to differentiate New Zealand (NZ) honey from that of international origin. Twenty elements were analysed by ICP-MS in 352 honeys from 34 various countries. Of these, 323 honeys (245 New Zealand honeys, 78 international) and two subsets of data (NZ and European origin, n = 306, and, NZ and Denmark/Germany, n = 280) were visualised using principal component analysis (PCA). For the NZ/Europe subset, 42.2% of data was explained in the first two principal components. Statistical classification rules were also derived using linear discriminant analysis (LDA) and decision tree analysis. Various combinations of elements were explored for classification, considering the effect of soil-derived elements and those from anthropogenic sources. A high degree of accuracy (at least 90%) for the characterisation of New Zealand honey was observed for all statistical models, showing the robustness of these analyses. When using decision tree analysis to distinguish New Zealand samples from international samples, a tree with five terminal nodes (using Cs, Ba and Rb) was created with 92.4% accuracy. This work has demonstrated that elemental fingerprints of honey are a promising tool for categorising New Zealand honey from other geographical locations.

Using Natural Radionuclides to Trace Sources of Suspended Particles in the Lower Reaches of the Yellow River - Han Zhang; C. William Burnett; Xiaojie Zhang; Shibin Zhao; Disong Yang; Haiming Nan; Zhigang Yu; Bochao Xu (Journal of Ocean University of China, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Authigenic clay mineral constraints on spatiotemporal evolution of restricted, evaporitic conditions during deposition of the Ediacaran Doushantuo Formation - Shujun Han; Stefan C Löhr; April N Abbott; Andre Baldermann; Graham A. Shields; Huan Cui; Alan J Kaufman; Bo Chen; Bingsong Yu (Earth and Planetary Science Letters, 2024)

Fani Maoré, a new “young HIMU” volcano with extreme geochemistry - Catherine Chauvel; Edward C. Inglis; Pamela Gutierrez; Tu-Han Luu; Pierre Burckel; Pascale Besson (Earth and Planetary Science Letters, 2024)

Diversity and connectedness of brine shrimp viruses in global hypersaline ecosystems - Xuan Dong; Cixiu Li; Yiting Wang; Tao Hu; Fan Zhang; Fanzeng Meng; Meirong Gao; Xuekai Han; Guohao Wang; Jiahao Qin; Hans Nauwynck; Edward C. Holmes; et al. (Science China Life Sciences, 2024)

Time-dependent variation in oral irritation subqualities of capsaicin solution: Using Time-Intensity-Rate-All-That-Apply (TI-RATA) and temporal Check-All-That-Apply (TCATA) methods - Ragita C. Pramudya; Han-Seok Seo (Food Quality and Preference, 2023)

Model-guided design and optimization of CPA perfusion protocols for whole organ cryopreservation - Zonghu Han; Joseph S. Rao; Srivasupradha Ramesh; Jan Hergesell; Bat-Erdene Namsrai; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Cryobiology, 2023)

SUCCESSFUL TRANSPLANT OF KIDNEYS AFTER VITRIFICATION AND NANOWARMING - Zonghu Han; Joseph S. Rao; Lakshya Gangwar; Bat-Erdene Namsrai; Jacqueline Pasek-Allen; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Cryobiology, 2023)

Assessing cellular and organ-level health, viability, and function of vitrified kidneys and islets for transplantation - Joseph Sushil Rao; Zonghu Han; Li Zhan; Michael L. Ethridge; John C. Bischof; Erik B. Finger (Cryobiology, 2023)

Sensorimotor Cough Dysfunction in Cerebellar Ataxias - Emilie R. Lowell; James C. Borders; Sarah E. Perry; Avery E. Dakin; Jordanna S. Sevitz; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2023)

Effect of pressure on the supercritical solvent impregnation of pomegranate peel extract into low-density polyethylene films - Han Lyn F; Nor Adilah A; Gun Hean C; Nur Hanani Z.A (Journal of Food Engineering, 2023)

Spatially heterogenous seawater δ34S and global cessation of Ca-sulfate burial during the Toarcian oceanic anoxic event - Zhong Han; Xiumian Hu; Robert J. Newton; Tianchen He; Benjamin J.W. Mills; Hugh C. Jenkyns; Micha Ruhl; Robert A. Jamieson (Earth and Planetary Science Letters, 2023)

Cell-Free DNA as a Biomarker in a Rodent Model of Chlorpyrifos Poisoning Causing Mitochondrial Dysfunction - Shih-Han Kao; Frances S. Shofer; John C. Greenwood; Oladunni Alomaja; Abhay Ranganathan; Sarah Piel; Clementina Mesaros; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

CHD7 variants associated with hearing loss and enlargement of the vestibular aqueduct - Isabelle Roux; Cristina Fenollar-Ferrer; Hyun Jae Lee; Parna Chattaraj; Ivan A. Lopez; Kyungreem Han; Keiji Honda; Carmen C. Brewer; John A. Butman; Robert J. Morell; Donna M. Martin; Andrew J. Griffith (Human Genetics, 2023)
Enlargement of the endolymphatic sac, duct, and vestibular aqueduct (EVA) is the most common inner ear malformation identified in patients with sensorineural hearing loss. EVA is associated with pathogenic variants in SLC26A4. However, in European–Caucasian populations, about 50% of patients with EVA carry no pathogenic alleles of SLC26A4 . We tested for the presence of variants in CHD7 , a gene known to be associated with CHARGE syndrome, Kallmann syndrome, and hypogonadotropic hypogonadism, in a cohort of 34 families with EVA subjects without pathogenic alleles of SLC26A4 . In two families, NM_017780.4: c.3553A > G [p.(Met1185Val)] and c.5390G > C [p.(Gly1797Ala)] were detected as monoallelic CHD7 variants in patients with EVA. At least one subject from each family had additional signs or potential signs of CHARGE syndrome but did not meet diagnostic criteria for CHARGE. In silico modeling of these two missense substitutions predicted detrimental effects upon CHD7 protein structure. Consistent with a role of CHD7 in this tissue, Chd7 transcript and protein were detected in all epithelial cells of the endolymphatic duct and sac of the developing mouse inner ear. These results suggest that some CHD7 variants can cause nonsyndromic hearing loss and EVA. CHD7 should be included in DNA sequence analyses to detect pathogenic variants in EVA patients. Chd7 expression and mutant phenotype data in mice suggest that CHD7 contributes to the formation or function of the endolymphatic sac and duct.

Model-Guided Design and Optimization of CPA Perfusion Protocols for Whole Organ Cryopreservation - Zonghu Han; Joseph Sushil Rao; Srivasupradha Ramesh; Jan Hergesell; Bat-Erdene Namsrai; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Annals of Biomedical Engineering, 2023)
Vitrification could enable long-term organ preservation, but only after loading high-concentration, potentially toxic cryoprotective agents (CPAs) by perfusion. In this paper, we combine a two-compartment Krogh cylinder model with a toxicity cost function to theoretically optimize the loading of CPA (VMP) in rat kidneys as a model system. First, based on kidney perfusion experiments, we systematically derived the parameters for a CPA transport loading model, including the following: V b = 86.0% ( r a = 3.86 μm), L p = 1.5 × 10 –14 m 3 /(N·s), ω = 7.0 × 10 –13 mol/(N·s), σ = 0.10. Next, we measured the toxicity cost function model parameters as α = 3.12 and β = 9.39 × 10 –6 . Combining these models, we developed an improved kidney-loading protocol predicted to achieve vitrification while minimizing toxicity. The optimized protocol resulted in shorter exposure (25 min or 18.5% less) than the gold standard kidney-loading protocol for VMP, which had been developed based on decades of empirical practice. After testing both protocols on rat kidneys, we found comparable physical and biological outcomes. While we did not dramatically reduce toxicity, we did reduce the time. As our approach is now validated, it can be used on other organs lacking defined toxicity data to reduce CPA exposure time and provide a rapid path toward developing CPA perfusion protocols for other organs and CPAs.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Intakes of Unprocessed and Minimally Processed and Ultraprocessed Food Are Associated with Diet Quality in Female and Male Health Professionals in the United States: A Prospective Analysis - Sinara Laurini Rossato; Neha Khandpur; Chun-Han Lo; Stela Maris Jezus Castro; Jean Philippe Drouin-Chartier; Laura Sampson; Changzheng Yuan; Cristiane Murta-Nascimento; Maria Antonieta Carvalhaes; Carlos Augusto Monteiro; Qi Sun; Teresa T. Fung; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Paleocurrent and paleowind direction reconstruction research progress and perspectives: a review - F. Y. Zhao; C. L. Hu; C. C. Han; Y. Q. Dong; Q. X. Yuan (Australian Journal of Earth Sciences, 2023)

Micro/nanoscale bone char alleviates cadmium toxicity and boosts rice growth via positively altering the rhizosphere and endophytic microbial community - Anqi Liang; Chuanxin Ma; Jiang Xiao; Yi Hao; Hao Li; Yaozu Guo; Yini Cao; Weili Jia; Lanfang Han; Guangcai Chen; Qian Tan; Jason C. White; et al. (Journal of Hazardous Materials, 2023)

Life stage affects prey use with fitness consequences in a zoophytophagous mirid bug - Ruo-han Ma; Jia-min Gu; Coline C. Jaworski; Zheng-xuan Xue; Xue-ling Li; Pei-ling Wang; Peng Han; Nicolas Desneux (Phytoparasitica, 2023)

Aquatic photolysis of high-risk chemicals of emerging concern from secondary effluent mediated by sunlight irradiation for ecological safety and the enhanced methods - Danyang Li; Xiaoyan Y. Ma; Shiying Zhang; Yongkun K. Wang; Yingnan Han; Rong Chen; Xiaochang C. Wang; Huu Hao Ngo (Water Research, 2023)

Electroconductive and mechano-competent PUCL@CNT nanohybrid scaffolds guiding neuronal specification of neural stem/progenitor cells - Yu-Meng Li; Kapil D. Patel; Yoon-Koo Han; Suk-Min Hong; Yu-Xuan Meng; Hae-Hyoung Lee; Jeong Hui Park; Jonathan C. Knowles; Jung Keun Hyun; Jung-Hwan Lee; Hae-Won Kim (Chemical Engineering Journal, 2023)

A cross sectional pilot study to assess the role of phthalates on respiratory morbidity among patients with chronic obstructive pulmonary disease - Lesliam Quirós-Alcalá; Daniel C. Belz; Han Woo; Wendy Lorizio; Nirupama Putcha; Kirsten Koehler; Meredith C. McCormack; Nadia N. Hansel (Environmental Research, 2023)

Hyaluronic acid microparticles for effective spheroid culture and transplantation in liver tissue - Kyoung Hwan Park; Bokyeong Ryu; Jin Jung Song; Hye-Eun Shim; Sun-Sook Song; Ji-Seok Han; C-Yoon Kim; Kang Moo Huh; Sun-Woong Kang (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Global patterns and drivers of leaf photosynthetic capacity: The relative importance of environmental factors and evolutionary history - Zhengbing Yan; Jordi Sardans; Josep Peñuelas; Matteo Detto; Nicholas G. Smith; Han Wang; Lulu Guo; Alice C. Hughes; Zhengfei Guo; Calvin K. F. Lee; Lingli Liu; Jin Wu (Global Ecology and Biogeography, 2023)
Aim Understanding the considerable variability and drivers of global leaf photosynthetic capacity [indicated by the maximum carboxylation rate standardized to 25°C ( V c,max25 )] is an essential step for accurate modelling of terrestrial plant photosynthesis and carbon uptake under climate change. Although current environmental conditions have often been connected with empirical and theoretical models to explain global V c,max25 variability through acclimatization and adaptation, long‐term evolutionary history has largely been neglected, but might also explicitly play a role in shaping the V c,max25 variability. Location Global. Time period Contemporary. Major taxa studied Terrestrial plants. Methods We compiled a geographically comprehensive global dataset of V c,max25 for C 3 plants ( n = 6917 observations from 2157 species and 425 sites covering all major biomes world‐wide), explored the biogeographical and phylogenetic patterns of V c,max25 , and quantified the relative importance of current environmental factors and evolutionary history in driving global V c,max25 variability. Results We found that V c,max25 differed across different biomes, with higher mean values in relatively drier regions, and across different life‐forms, with higher mean values in non‐woody relative to woody plants and in legumes relative to non‐leguminous plants. The values of V c,max25 displayed a significant phylogenetic signal and diverged in a contrasting manner across phylogenetic groups, with a significant trend along the evolutionary axis towards a higher V c,max25 in more modern clades. A Bayesian phylogenetic linear mixed model revealed that evolutionary history (indicated by phylogeny and species) explained nearly 3‐fold more of the variation in global V c,max25 than present‐day environment (53 vs. 18%). Main conclusions These findings contribute to a comprehensive assessment of the patterns and drivers of global V c,max25 variability, highlighting the importance of evolutionary history in driving global V c,max25 variability, hence terrestrial plant photosynthesis.

Transfer learning in a biomaterial fibrosis model identifies in vivo senescence heterogeneity and contributions to vascularization and matrix production across species and diverse pathologies - Christopher Cherry; James I. Andorko; Kavita Krishnan; Joscelyn C. Mejías; Helen Hieu Nguyen; Katlin B. Stivers; Elise F. Gray-Gaillard; Anna Ruta; Jin Han; Naomi Hamada; Masakazu Hamada; Ines Sturmlechner; et al. (GeroScience, 2023)

Comparing “apples” and “oranges” in the Woodford Shale: Pitfalls of the thermal maturity gradient approach for constraining evolution of mudrock porosity - Elizabeth T. Baruch; Stefan C. Löhr; Shujun Han; David N. Dewhurst; Alan S. Collins (Marine and Petroleum Geology, 2023)

Genetic nurture in educational attainment - John Cawley; Euna Han; Jiyoon Kim; Edward C. Norton (Economics & Human Biology, 2023)

Preclinical safety assessment of the suction-assisted intradermal injection of the SARS-CoV-2 DNA vaccine candidate pGO-1002 in white rabbit - Seunghee Oh; Min Seong Jang; Kyung Jin Jung; Ji-Seok Han; Hyojin Lee; Areum Gil; Bohyun Jeon; Christine C. Roberts; Joel N. Maslow; Yong-Bum Kim; Kang-Hyun Han (Archives of Toxicology, 2023)

Life cycle-carbon footprints for environmental performance/labeling of crop-based food products: analyses of complementary functional units and hotspots - N. C. O; S. C. Pak; R. J. Ri; H. I. Han (International Journal of Environmental Science and Technology, 2023)

Correction: Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Alteration in Cerebral Metabolism in a Rodent Model of Acute Sub-lethal Cyanide Poisoning - Oladunni Alomaja; Frances S. Shofer; John C. Greenwood; Sarah Piel; Carly Clayman; Clementina Mesaros; Shih-Han Kao; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

The metamicrobiome: key determinant of the homeostasis of nutrient recycling - Inger K. de Jonge; Michiel P. Veldhuis; J. Hans C. Cornelissen; Matty P. Berg; Han Olff (Trends in Ecology & Evolution, 2023)

Nanomaterials in agricultural soils: Ecotoxicity and application - Chuanxin Ma; Lanfang Han; Heping Shang; Yi Hao; Xinxin Xu; Jason C. White; Zhenyu Wang; Baoshan Xing (Current Opinion in Environmental Science & Health, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

ZnO quantum dots outperform nanoscale and bulk particles for enhancing tomato (Solanum lycopersicum) growth and nutritional values - Min Sun; Chenchen Zhao; Heping Shang; Yi Hao; Lanfang Han; Kun Qian; Jason C. White; Chuanxin Ma; Baoshan Xing (Science of The Total Environment, 2023)

Potential health and economic impacts of shifting manufacturing from China to Indonesia or India - Qi Ran; Shao-Yi Lee; Duofan Zheng; Han Chen; Shili Yang; John C. Moore; Wenjie Dong (Science of The Total Environment, 2023)

Understanding caldera degassing from a detailed investigation at Lake Rotoiti, Okataina Volcanic Centre, New Zealand - Tsung-Han Jimmy Yang; Isabelle Chambefort; Agnes Mazot; Michael C. Rowe; Brad Scott; Nick Macdonald; Cynthia Werner; Tobias P. Fischer; Cornel E.J. de Ronde (Journal of Volcanology and Geothermal Research, 2023)

Implementation of a dialogue-based food safety education program for low-income families - Han Chen; Juan C. Archila-Godínez; Leah Klinestiver; Lia Rosa; Tressie Barrett; Virgilia Zabala; Yaohua Feng (Food Control, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Seasonal effects of urban morphology on land surface temperature in a three-dimensional perspective: A case study in Hangzhou, China - Sijia Han; Hao Hou; Ronald C. Estoque; Yaoyao Zheng; Chuhui Shen; Yuji Murayama; Jing Pan; Ben Wang; Tangao Hu (Building and Environment, 2023)

Correction to: Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2023)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Duration- and sex-dependent neural circuit control of voluntary physical activity - Margaret K. Tanner; Jazmyne K. P. Davis; Jennifer Jaime; Nicolette A. Moya; Alyssa A. Hohorst; Kelsey Bonar; Kelsey A. Abrams; Nashra Jamil; Rebecca Han; Troy J. Hubert; Nadja Brown; Esteban C. Loetz; et al. (Psychopharmacology, 2022)

Genetic diversity, lineage divergence, and demography of Diaphanosoma dubium (Crustacea: Cladocera) on Hainan Island, China - Ping Liu; Xiaoli Zhang; Qi Huang; Eric Zeus C. Rizo; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2022)

A Two-Stage Path Planning Algorithm Based on Rapid-Exploring Random Tree for Ships Navigating in Multi-Obstacle Water Areas Considering COLREGs - Jinfen Zhang; Han Zhang; Jiongjiong Liu; Da Wu; C. Guedes Soares (Journal of Marine Science and Engineering, 2022)
A two-stage ship path planning method is proposed, based on the Rapid-exploring Random Tree (RRT) algorithm, which is composed of global path planning and local path planning, addressing the important problem of finding an economical and safe path from start to destination for ships under dynamic environment, especially in waters with multiple obstacles and multiple target ships. The global path planning takes into consideration the ship draft and Under Keel Clearance to find navigable water using RRT, and reduces the path length and waypoints based on elliptic sampling and smoothing. In the local path planning, a dynamic collision risk detection model is constructed by introducing the Quaternion Ship Domain under a dynamic environment, and the restrictions of ship manoeuvrability and COLREGs are also involved. The simulation results show that the proposed model can find a satisfactory path within a few iterations, and keep clear of both static obstacles and dynamic ships. The research can be used to make and verify planned ship routes before sailing and to guide officers to make decisions regarding collision avoidance.

Patient Perspectives on the Risk-Based NLST Outcomes Tool for Lung Cancer Screening - Megan C. Roberts; Elizabeth L. Seaman; William M. P. Klein; Rebecca A. Ferrer; Paul K.J. Han; Hormuzd A. Katki; Stephanie R. Land; Robert A. Liotta; Joel A. Nations; P. Gabriel Peterson (Journal of Cancer Education, 2022)

Spray-Dried and Spray-Freeze-Dried Powder Formulations of an Anti-Interleukin-4Rα Antibody for Pulmonary Delivery - Harry W. Pan; Han Cong Seow; Jason C. K. Lo; Jinlin Guo; Lingqiao Zhu; Susan W. S. Leung; Chenghai Zhang; Jenny K. W. Lam (Pharmaceutical Research, 2022)

Pore development in terrestrial shale reservoirs: the Permian Lucaogou Formation, Junggar Basin, northwestern China - Y. Jin; J. Tian; C. Han; H. Liu; L. Dong; S. Dan (Australian Journal of Earth Sciences, 2022)

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Factors associated with symptoms of poor mental health among women factory workers in China’s supply chain - K. K. Sznajder; S. D. Harlow; J. Wang; L. Tso; Y. Ashagre; C. Han (International Archives of Occupational and Environmental Health, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2022)

Mechanical properties and fracture evolution process of Beishan granite under tensile state - C. S. Wang; J. F. Liu; Y. W. Zhao; S. J. Han (Bulletin of Engineering Geology and the Environment, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Identification and Verification of the Ability of Cdk5 to Phosphorylate Deubiquitinating Enzyme BRCC3 In Vitro - C. H. Zhang; K. Qin; S. L. Tian; Y. Han; S. Y. Xu; X. Y. Shao (Bulletin of Experimental Biology and Medicine, 2022)

Correction to: Profiling Basal Forebrain Cholinergic Neurons Reveals a Molecular Basis for Vulnerability Within the Ts65Dn Model of Down Syndrome and Alzheimer’s Disease - Melissa J. Alldred; Sai C. Penikalapati; Sang Han Lee; Adriana Heguy; Panos Roussos; Stephen D. Ginsberg (Molecular Neurobiology, 2022)

Current management of melanoma patients with nodal metastases - Dale Han; Alexander C. J. van Akkooi; Richard J. Straker; Adrienne B. Shannon; Giorgos C. Karakousis; Lin Wang; Kevin B. Kim; Douglas Reintgen (Clinical & Experimental Metastasis, 2022)

Integrated pest management of Tuta absoluta: practical implementations across different world regions - Nicolas Desneux; Peng Han; Ramzi Mansour; Judit Arnó; Thierry Brévault; Mateus R. Campos; Anais Chailleux; Raul N. C. Guedes; Javad Karimi; Kouassi Arthur J. Konan; Anne-violette Lavoir; María G. Luna; et al. (Journal of Pest Science, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

Novel 1,2,4-triazole analogues as mushroom tyrosinase inhibitors: synthesis, kinetic mechanism, cytotoxicity and computational studies - Balasaheb D. Vanjare; Prasad G. Mahajan; Nilam C. Dige; Hussain Raza; Mubashir Hassan; Yohan Han; Song Ja Kim; Sung-Yum Seo; Ki Hwan Lee (Molecular Diversity, 2021)

The second wave of earthworm invasions in North America: biology, environmental impacts, management and control of invasive jumping worms - Chih-Han Chang; Marie L. C. Bartz; George Brown; Mac A. Callaham; Erin K. Cameron; Andrea Dávalos; Annise Dobson; Josef H. Görres; Bradley M. Herrick; Hiroshi Ikeda; Samuel W. James; Marie R. Johnston; et al. (Biological Invasions, 2021)

Dietary Supplementation of Bacillus sp. SJ-10 and Lactobacillus plantarum KCCM 11322 Combinations Enhance Growth and Cellular and Humoral Immunity in Olive Flounder (Paralichthys olivaceus) - Md Tawheed Hasan; Won Je Jang; Bong-Joo Lee; Sang Woo Hur; Sang Gu Lim; Kang Woong Kim; Hyon-Sob Han; Eun-Woo Lee; Sungchul C Bai; In-Soo Kong (Probiotics and Antimicrobial Proteins, 2021)

Profiling Basal Forebrain Cholinergic Neurons Reveals a Molecular Basis for Vulnerability Within the Ts65Dn Model of Down Syndrome and Alzheimer’s Disease - Melissa J. Alldred; Sai C. Penikalapati; Sang Han Lee; Adriana Heguy; Panos Roussos; Stephen D. Ginsberg (Molecular Neurobiology, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Drought tolerance in selected aerobic and upland rice varieties is driven by different metabolic and antioxidative responses - Giovanni Melandri; Hamada AbdElgawad; Kristýna Floková; Diaan C. Jamar; Han Asard; Gerrit T. S. Beemster; Carolien Ruyter-Spira; Harro J. Bouwmeester (Planta, 2021)
Main conclusions Sugar-mediated osmotic acclimation and a strong antioxidative response reduce drought-induced biomass loss at the vegetative stage in rice. Abstract A clear understanding of the physiological and biochemical adaptations to water limitation in upland and aerobic rice can help to identify the mechanisms underlying their tolerance to low water availability. In this study, three indica rice varieties-IR64 (lowland), Apo (aerobic), and UPL Ri-7 (upland)-, that are characterized by contrasting levels of drought tolerance, were exposed to drought at the vegetative stage. Drought-induced changes in biomass, leaf metabolites and oxidative stress markers/enzyme activities were analyzed in each variety at multiple time points. The two drought-tolerant varieties, Apo and UPL Ri-7 displayed a reduced water use in contrast to the susceptible variety IR64 that displayed high water consumption and consequent strong leaf dehydration upon drought treatment. A sugar-mediated osmotic acclimation in UPL Ri-7 and a strong antioxidative response in Apo were both effective in limiting the drought-induced biomass loss in these two varieties, while biomass loss was high in IR64, also after recovery. A qualitative comparison of these results with the ones of a similar experiment conducted in the field at the reproductive stage showed that only Apo, which also in this stage showed the highest antioxidant power, was able to maintain a stable grain yield under stress. Our results show that different metabolic and antioxidant adaptations confer drought tolerance to aerobic and upland rice varieties in the vegetative stage. The effectiveness of these adaptations differs between developmental stages. Unraveling the genetic control of these mechanisms might be exploited in breeding for new rice varieties adapted to water-limited environments.

Current distribution and habitat models of the yellow-throated marten, Martes flavigula, in South Korea - Hwa-Jin Lee; Oh-Sun Lee; Dong-Gul Woo; Han-Na Kim; Mark C. Wallace; Yeong-Seok Jo (Mammal Research, 2021)

Editorial: Designing a Protocol Adopting an Artificial Intelligence (AI)–Driven Approach for Early Diagnosis of Late-Onset Alzheimer’s Disease - Victor O. K. Li; Jacqueline C. K. Lam; Yang Han; Lawrence Y. L. Cheung; Jocelyn Downey; Tushar Kaistha; Illana Gozes (Journal of Molecular Neuroscience, 2021)

Transgenerational conditioned male fertility of HD-ZIP IV transcription factor mutant ocl4: impact on 21-nt phasiRNA accumulation in pre-meiotic maize anthers - Pranjal Yadava; Saleh Tamim; Han Zhang; Chong Teng; Xue Zhou; Blake C. Meyers; Virginia Walbot (Plant Reproduction, 2021)

Application of two-level design method on subway tunnel crossing active fault: a case study on Urumqi subway tunnel intersected by reverse fault dislocation - S. An; L. J. Tao; X. C. Han; Y. Zhang (Bulletin of Engineering Geology and the Environment, 2021)

ValSten: a new wild species derived allotetraploid for increasing genetic diversity of the peanut crop (Arachis hypogaea L.) - Dongying Gao; Ana C. G. Araujo; Eliza F. M. B. Nascimento; M. Carolina Chavarro; Han Xia; Scott A. Jackson; David J. Bertioli; Soraya C. M. Leal-Bertioli (Genetic Resources and Crop Evolution, 2021)
Introgression of desirable traits from wild relatives plays an important role in crop improvement, as wild species have important characters such as high resistance to pests and pathogens. However, use of wild peanut relatives is challenging because almost all wild species are diploid and sexually incompatible with cultivated peanut, which is tetraploid (AABB genome type; 2 n = 4x = 40). To overcome the ploidy barrier, we used 2 wild species to make a tetraploid with the same allotetraploid genome composition as cultivated peanut. Crosses were made between 2 diploid wild species, Arachis valida Krapov. and W.C. Greg. (BB genome; 2 n = 2x = 20) and Arachis stenosperma Krapov. and W.C. Greg. (AA genome; 2 n = 2x = 20). Cuttings from the diploid F 1 AB hybrid were treated with colchicine to induce chromosome doubling thus generating an induced allotetraploid. Chromosome counts confirmed polyploidy (AABB genome; 2 n = 4x = 40). We named the new allotetraploid ValSten. Plants had well-developed fertile pollen, produced abundant seed and were sexually compatible with cultivated peanut. ValSten exhibits the same high resistance to early and late leaf spot and rust as its diploid parents. Notably, we observed morphological variations, including flower width and branch angles in the earliest generation (S 0 ) of allotetraploids. A SNP array was used to genotype 47 S 0 allotetraploids. The great majority of markers showed the additive allelic state from both parents (AABB). However, some loci were AAAA or BBBB, indicating homeologous recombination. ValSten provides a new, vigorous, highly fertile, disease resistant germplasm for peanut research and improvement.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

Docosahexaenoic Acid (DHA) Supplementation Alters Phospholipid Species and Lipid Peroxidation Products in Adult Mouse Brain, Heart, and Plasma - Grace Y. Sun; Michael K. Appenteng; Runting Li; Taeseon Woo; Bo Yang; Chao Qin; Meixia Pan; Magdalena Cieślik; Jiankun Cui; Kevin L. Fritsche; Zezong Gu; Matthew Will; et al. (NeuroMolecular Medicine, 2021)

Gga-miR-181a modulates ANP32A expression and inhibits MDCC-MSB-1 cell - X. Li; C. Zhao; B. Han; L. Qu; C. Liu; N. Yang; L. Lian (In Vitro Cellular & Developmental Biology - Animal, 2021)

Nano-selenium Supplementation Increases Selenoprotein (Sel) Gene Expression Profiles and Milk Selenium Concentration in Lactating Dairy Cows - Liqiang Han; Kun Pang; Tong Fu; Clive J. C. Phillips; Tengyun Gao (Biological Trace Element Research, 2021)
Supplementation with selenium is common for dairy cows, but the importance of selenium source is not clear. This study aimed to compare nano-selenium (Nano-Se) and sodium selenite supplements for dairy cows on lactation performance, milk Se levels and selenoprotein (Sel) gene expression. Twelve multiparous Holstein cows were randomly divided into two groups: a control group fed a basal diet plus 0.30 mg Se/kg of DM as sodium selenite or Nano-Se for 30 days. Dry matter intake, milk yield and composition were not affected by dietary Se source ( P > 0.05); however, the milk total Se levels and milk glutathione peroxidase (GSH-Px) activities were higher with Nano-Se supplementation than sodium selenite ( P < 0.05). At the end of the experiment, Nano-Se supplementation significantly increased plasma Se levels and GSH-Px activity, compared with the sodium selenite supplement. The mRNA expression levels of glutathione peroxidase 1, 2 and 4; thioredoxin reductase 2 and 3; and selenoproteins W, T, K and F were markedly upregulated ( P < 0.05) in the mammary gland of the Nano-Se group. Thus, the source of selenium plays an important role in the antioxidant status and in particular the Sel gene expression in the mammary glands of dairy cows, both being stimulated by nano sources.

Cycling in degradation of organic polymers and uptake of nutrients by a litter‐degrading fungus - Aurin M. Vos; Robert‐Jan Bleichrodt; Koen C. Herman; Robin A. Ohm; Karin Scholtmeijer; Heike Schmitt; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2021)
Summary Wood and litter degrading fungi are the main decomposers of lignocellulose and thus play a key role in carbon cycling in nature. Here, we provide evidence for a novel lignocellulose degradation strategy employed by the litter degrading fungus Agaricus bisporus (known as the white button mushroom). Fusion of hyphae allows this fungus to synchronize the activity of its mycelium over large distances (50 cm). The synchronized activity has a 13‐h interval that increases to 20 h before becoming irregular and it is associated with a 3.5‐fold increase in respiration, while compost temperature increases up to 2°C. Transcriptomic analysis of this burst‐like phenomenon supports a cyclic degradation of lignin, deconstruction of (hemi‐) cellulose and microbial cell wall polymers, and uptake of degradation products during vegetative growth of A. bisporus . Cycling in expression of the ligninolytic system, of enzymes involved in saccharification, and of proteins involved in nutrient uptake is proposed to provide an efficient way for degradation of substrates such as litter.

Dissociable dopaminergic and pavlovian influences in goal-trackers and sign-trackers on a model of compulsive checking in OCD - D. M. Eagle; C. Schepisi; S. Chugh; S. Desai; S. Y. S. Han; T. Huang; J. J. Lee; C. Sobala; W. Ye; A. L. Milton; T. W. Robbins (Psychopharmacology, 2020)
Rationale Checking is a functional behaviour that provides information to guide behaviour. However, in obsessive-compulsive disorder (OCD), checking may escalate to dysfunctional levels. The processes underpinning the transition from functional to dysfunctional checking are unclear but may be associated with individual differences that support the development of maladaptive behaviour. We examined one such predisposition, sign-tracking to a pavlovian conditioned stimulus, which we previously found associated with dysfunctional checking. How sign-tracking interacts with another treatment with emerging translational validity for OCD-like checking, chronic administration of the dopamine D 2 receptor agonist quinpirole, is unknown. Objectives We tested how functional and dysfunctional checking in the rat observing response task (ORT) was affected by chronic quinpirole administration in non-autoshaped controls and autoshaped animals classified as sign-trackers or goal-trackers. Methods Sign-trackers or goal-trackers were trained on the ORT before the effects of chronic quinpirole administration on checking were assessed. Subsequently, the effects on checking of different behavioural challenges, including reward omission and the use of unpredictable reinforcement schedules, were tested. Results Prior autoshaping increased checking. Sign-trackers and goal-trackers responded differently to quinpirole sensitization, reward omission and reinforcement uncertainty. Sign-trackers showed greater elevations in dysfunctional checking, particularly during uncertainty. By contrast, goal-trackers predominantly increased functional checking responses, possibly in response to reduced discrimination accuracy in the absence of cues signalling which lever was currently active. Conclusions The results are discussed in terms of how pavlovian associations influence behaviour that becomes compulsive in OCD and how this may be dependent on striatal dopamine D 2 receptors.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Improving the Diagnostic Ability of the Sleep Apnea Screening System Based on Oximetry by Using Physical Activity Data - Cheng-Han Wu; Jui-Hsuan Lee; Terry B. J. Kuo; Chun-Ting Lai; Lieber P. H. Li; Cheryl C. H. Yang (Journal of Medical and Biological Engineering, 2020)

Dietary exposure assessment of cadmium, arsenic, and lead in market rice from Sri Lanka - Lin Liu; Jialiang Han; Xiaohang Xu; Zhidong Xu; Kasun S. Abeysinghe; Anjana J. Atapattu; P. Mangala C. S. De Silva; Qinhui Lu; Guangle Qiu (Environmental Science and Pollution Research, 2020)

Zooplankton in a continuous waterscape: environmental and spatial factors shaping spring zooplankton community structure in a large canyon reservoir at the tropic of cancer - Eric Zeus C. Rizo; Ping Liu; Haiyu Niu; Yang Yang; Qiuqi Lin; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2020)

Genome-wide analysis of brassinosteroid responsive small RNAs in Arabidopsis thaliana - So Young Park; Jae-Han Choi; Dong-Ha Oh; John C. Johnson; Maheshi Dassanayake; Dong-Hoon Jeong; Man-Ho Oh (Genes & Genomics, 2020)

Carbapenem-resistant Enterobacteriaceae in patients with bacteraemia at tertiary hospitals in South Africa, 2015 to 2018 - O. Perovic; H. Ismail; V. Quan; C. Bamford; T. Nana; V. Chibabhai; P. Bhola; P. Ramjathan; K. Swe Swe-Han; J. Wadula; A. Whitelaw; M. Smith; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Glycosaminoglycan remodeling during chondrogenic differentiation of human bone marrow−/synovial-derived mesenchymal stem/stromal cells under normoxia and hypoxia - João C. Silva; Xiaorui Han; Teresa P. Silva; Ke Xia; Paiyz E. Mikael; Joaquim M. S. Cabral; Frederico Castelo Ferreira; Robert J. Linhardt (Glycoconjugate Journal, 2020)

Targeting Two Antigens Associated with B-ALL with CD19-CD123 Compound Car T Cell Therapy - Lulu E. Yan; Hongyu Zhang; Masayuki Wada; Liu Fang; Jia Feng; Wenli Zhang; Qi Chen; Yuanzhen Cao; Kevin G. Pinz; Kevin H. Chen; Jessica C. Petrov; Xi Chen; et al. (Stem Cell Reviews and Reports, 2020)

Reciprocal comparison of geodetically sensed and modeled vertical hydrological loading products - Vagner G. Ferreira; Zhiqiang Liu; Henry C. Montecino; Peng Yuan; Caleb I. Kelly; Abubakar S. Mohammed; Lu Y. Han (Acta Geodaetica et Geophysica, 2020)

Role of Adult Tissue-Derived Pluripotent Stem Cells in Bone Regeneration - Liudmila Leppik; K. Sielatycka; D. Henrich; Z. Han; H. Wang; M. J. Eischen-Loges; K. M. C. Oliveira; M. B. Bhavsar; M. Z. Ratajczak; J. H. Barker (Stem Cell Reviews and Reports, 2020)
Background Bone marrow-derived mononuclear cells (BM-MNC) consist of a heterogeneous mix of mesenchymal stem cells (MSC), hematopoietic progenitor cells (HPC), endothelial progenitor cells (EPC), monocytes, lymphocytes and pluripotent stem cells. Whereas the importance of MSC and EPC has been well documented in bone healing and regeneration studies, the role of pluripotent stem cells is still poorly understood. In the present study we evaluated if and how Very Small Embryonic Like cells (VSEL), isolated from rat BM-MNC, contribute to bone healing. Methods Large bone defects were made in the femurs of 38 Sprague Dawley female rats and treated with β-TCP scaffold granules seeded with male VSEL; BM-MNC, VSEL-depleted BM-MNC or scaffold alone, and bone healing was evaluated at 8 weeks post-surgery. Results Bone healing was significantly increased in defects treated with VSEL and BM-MNC, compared to defects treated with VSEL-depleted BM-MNC. Donor cells were detected in new bone tissue, in all the defects treated with cells, and in fibrous tissue only in defects treated with VSEL-depleted BM-MNC. The number of CD68+ cells was the highest in the VSEL-depleted group, whereas the number of TRAP positive cells was the lowest in this group. Conclusions Based on the results, we can conclude that VSEL play a role in BM-MNC induced bone formation. In our rat femur defect model, in defects treated with VSEL-depleted BM-MNC, osteoclastogenesis and bone formation were decreased, and foreign body reaction was increased.

Exchange protein directly activated by cAMP (Epac) 1 plays an essential role in stress-induced exercise capacity by regulating PGC-1α and fatty acid metabolism in skeletal muscle - Wai-Kin So; Hyoung Kyu Kim; Yingxian Chen; Seung Hun Jeong; Patrick Ka Kit Yeung; Billy C. K. Chow; Jin Han; Sookja K. Chung (Pflügers Archiv - European Journal of Physiology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Seed maturation and post-harvest ripening negatively affect arabidopsis somatic embryogenesis - Han Wu; Baojian Chen; Martijn Fiers; Justyna Wróbel-Marek; Jan Kodde; Steven P. C. Groot; Gerco Angenent; Hui Feng; Leónie Bentsink; Kim Boutilier (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Coniferization of the mixed‐wood boreal forests under warm climate - Cécile C. Remy; Dominic Senici; Han Y. H. Chen; Yves Bergeron; Martin Lavoie; Laure Paradis; Adam A. Ali (Journal of Quaternary Science, 2019)
Mixed‐wood boreal forests are characterized by a heterogeneous landscape dominated by coniferous or deciduous species depending on stand moisture and fire activity. Our study highlights the long‐term drivers of these differences between landscapes across mixed‐wood boreal forests to improve simulated vegetation dynamics under predicted climate changes. We investigate the effects of main climate trends and wildfire activities on the vegetation dynamics of two areas characterized by different stand moisture regimes during the last 9000 years. We performed paleofire and pollen analyses in the mixed‐wood boreal forest of north‐western Ontario, derived from lacustrine sediment deposits, to reconstruct historical vegetation dynamics, which encompassed both the Holocene climatic optimum ( ca . 8000–4000 a bp ) and the Neoglacial period ( ca . 4000 a bp ). The past warm and dry period (Holocene climatic optimum) promoted higher fire activity that resulted in an increase in coniferous species abundance in the xeric area. The predicted warmer climate and an increase in drought events should lead to a coniferization of the xeric areas affected by high fire activity while the mesic areas may retain a higher broadleaf abundance, as these areas are not prone to an increase in fire activity. Copyright © 2019 John Wiley & Sons, Ltd.

Rapid Increases in Bat Activity and Diversity after Wetland Construction in an Urban Ecosystem - Kevin A. Parker; Brian T. Springall; Reuben A. Garshong; Ashley N. Malachi; Lauren E. Dorn; Alicia Costa-Terryll; Rachael A. Mathis; Alayna N. Lewis; Cassandra L. MacCheyne; Tronjay T. Davis; Alexis D. Rice; Nyla Y. Varh; et al. (Wetlands, 2019)

Increased Diagnostic Yield of Spastic Paraplegia with or Without Cerebellar Ataxia Through Whole-Genome Sequencing - Aryun Kim; Kishore R. Kumar; Ryan L. Davis; Amali C. Mallawaarachchi; Velimir Gayevskiy; Andre E. Minoche; Zachary Walls; Han-Joon Kim; Mihee Jang; Mark J. Cowley; Ji-Hyun Choi; Chaewon Shin; et al. (The Cerebellum, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Local Application of Autologous Platelet-Rich Fibrin Patch (PRF-P) Suppresses Regulatory T Cell Recruitment in a Murine Glioma Model - Wojciech K. Panek; Katarzyna C. Pituch; Jason Miska; Julius W. Kim; Aida Rashidi; Deepak Kanojia; Aurora Lopez-Rosas; Yu Han; Dou Yu; Catalina Lee Chang; J. Robert Kane; Peng Zhang; et al. (Molecular Neurobiology, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

Phenotyping analysis of p53 knockout mice produced by gene editing and comparison with conventional p53 knockout mice - Ukjin Kim; C-Yoon Kim; Hanseul Oh; Ji Min Lee; Seo-Na Chang; Bokyeong Ryu; Jin Kim; Han-Woong Lee; Jae-Hak Park (Genes & Genomics, 2019)

Neuronal nitric oxide synthase activity mediates Lycium barbarum polysaccharides-enhanced sexual performance without stimulating noncontact erection in rats - Andy C. Huang; Jia-Min Wu; Ya-Han Chang; Navneet Kumar Dubey; Allen W. Chiu; Chien-Yu Yeh; Tung-Hu Tsai; Kuei-Ying Yeh (Psychopharmacology, 2019)

A high production of flavonoids and anthraquinones via adventitious root culture of Oplopanax elatus and evaluating antioxidant activity - L. Han; X. C. Piao; J. Jiang; X. L. Jiang; C. R. Yin; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Compositional and structural analysis of glycosaminoglycans in cell-derived extracellular matrices - João C. Silva; Marta S. Carvalho; Xiaorui Han; Ke Xia; Paiyz E. Mikael; Joaquim M. S. Cabral; Frederico Castelo Ferreira; Robert J. Linhardt (Glycoconjugate Journal, 2019)

Impact of Dairy Manure Processing Using Polyacrylamide on Antibiotic-Resistant Bacterial Level - Sunghwa Han; Sharon C. Long; Troy Runge; Cuihua Dong; Zong Liu (Water, Air, & Soil Pollution, 2019)

LIM kinase 1 acts as a profibrotic mediator in permanent atrial fibrillation patients with valvular heart disease - Qinhua Chen; Ryan C Gimple; Guannan Li; Jianzhou Chen; Han Wu; Ran Li; Jun Xie; Biao Xu (Journal of Biosciences, 2019)

Identification of phosphorylated proteins in response to salt stress in wheat embryo and endosperm during seed germination - X. Luo; C. Han; X. Deng; D. Zhu; Y. Liu; Y. Yan (Cereal Research Communications, 2019)

High frequency and diversity of parechovirus A in a cohort of Malawian children - Lieke Brouwer; Eveliina Karelehto; Alvin X. Han; Xiomara V. Thomas; Andrea H. L. Bruning; Job C. J. Calis; Michaël Boele van Hensbroek; Brenda M. Westerhuis; Darsha Amarthalingam; Sylvie M. Koekkoek; Sjoerd P. H. Rebers; Kamija S. Phiri; et al. (Archives of Virology, 2019)

Optimization of culture medium components and culture period for production of adventitious roots of Echinacea pallida (Nutt.) Nutt - Y. Gao; C. H. Wu; X. C. Piao; L. Han; R. Gao; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Electrophysiological Signatures of Intrinsic Functional Connectivity Related to rTMS Treatment for Mal de Debarquement Syndrome - Yoon-Hee Cha; Guofa Shou; Diamond Gleghorn; Benjamin C. Doudican; Han Yuan; Lei Ding (Brain Topography, 2018)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

Millennial multi-proxy reconstruction of oasis dynamics in Jordan, by the Dead Sea - Sebastian Eggenberger; Erika Gobet; Jacqueline F. N. van Leeuwen; Christoph Schwörer; Willem O. van der Knaap; Han F. van Dobben; Hendrik Vogel; Willy Tinner; Claire M. C. Rambeau (Vegetation History and Archaeobotany, 2018)

Forward modelling of global gravity fields with 3D density structures and an application to the high-resolution (~ 2 km) gravity fields of the Moon - M. Šprlák; S.-C. Han; W. E. Featherstone (Journal of Geodesy, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Determining species specific nightly bat activity in sites with varying urban intensity - Sarah A. Schimpp; Han Li; Matina C. Kalcounis-Rueppell (Urban Ecosystems, 2018)

Improved soil water deficit estimation through the integration of canopy temperature measurements into a soil water balance model - Ming Han; Huihui Zhang; José L. Chávez; Liwang Ma; Thomas J. Trout; Kendall C. DeJonge (Irrigation Science, 2018)

Heterotopic Purkinje Cells: a Comparative Postmortem Study of Essential Tremor and Spinocerebellar Ataxias 1, 2, 3, and 6 - Elan D. Louis; Sheng-Han Kuo; William J. Tate; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2018)

The FlbA-regulated predicted transcription factor Fum21 of Aspergillus niger is involved in fumonisin production - David Aerts; Esther E. Hauer; Robin A. Ohm; Mark Arentshorst; Wieke R. Teertstra; Christopher Phippen; Arthur F. J. Ram; Jens C. Frisvad; Han A. B. Wösten (Antonie van Leeuwenhoek, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

The China Plant Trait Database: toward a comprehensive regional compilation of functional traits for land plants - Han Wang; Sandy P. Harrison; Iain C. Prentice; Yanzheng Yang; Fan Bai; Henrique F. Togashi; Meng Wang; Shuangxi Zhou; Jian Ni (Ecology, 2018)
Plant functional traits provide information about adaptations to climate and environmental conditions, and can be used to explore the existence of alternative plant strategies within ecosystems. Trait data are also increasingly being used to provide parameter estimates for vegetation models. Here we present a new database of plant functional traits from China. Most global climate and vegetation types can be found in China, and thus the database is relevant for global modeling. The China Plant Trait Database contains information on morphometric, physical, chemical, and photosynthetic traits from 122 sites spanning the range from boreal to tropical, and from deserts and steppes through woodlands and forests, including montane vegetation. Data collection at each site was based either on sampling the dominant species or on a stratified sampling of each ecosystem layer. The database contains information on 1,215 unique species, though many species have been sampled at multiple sites. The original field identifications have been taxonomically standardized to the Flora of China. Similarly, derived photosynthetic traits, such as electron‐transport and carboxylation capacities, were calculated using a standardized method. To facilitate trait–environment analyses, the database also contains detailed climate and vegetation information for each site. The data set is released under a Creative Commons BY license. When using the data set, we kindly request that you cite this article, recognizing the hard work that went into collecting the data and the authors' willingness to make it publicly available.

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Global analysis of differentially expressed genes between japonica and indica rice roots reveals the molecular basis for enhanced cold tolerance in japonic a rice - Yo-Han Yoo; N. C. Anil Kumar; Jong-Chan Park; Sang-Won Lee; Ki-Hong Jung (Plant Biotechnology Reports, 2017)

Interannual variability of ecosystem carbon exchange: From observation to prediction - Shuli Niu; Zheng Fu; Yiqi Luo; Paul C. Stoy; Trevor F. Keenan; Benjamin Poulter; Leiming Zhang; Shilong Piao; Xuhui Zhou; Han Zheng; Jiayin Han; Qiufeng Wang; et al. (Global Ecology and Biogeography, 2017)
Aim Terrestrial ecosystems have sequestered, on average, the equivalent of 30% of anthropogenic carbon (C) emissions during the past decades, but annual sequestration varies from year to year. For effective C management, it is imperative to develop a predictive understanding of the interannual variability (IAV) of terrestrial net ecosystem C exchange (NEE). Location Global terrestrial ecosystems. Methods We conducted a comprehensive review to examine the IAV of NEE at global, regional and ecosystem scales. Then we outlined a conceptual framework for understanding how anomalies in climate factors impact ecological processes of C cycling and thus influence the IAV of NEE through biogeochemical regulation. Results The phenomenon of IAV in land NEE has been ubiquitously observed at global, regional and ecosystem scales. Global IAV is often attributable to either tropical or semi‐arid regions, or to some combination thereof, which is still under debate. Previous studies focus on identifying climate factors as driving forces of IAV, whereas biological mechanisms underlying the IAV of ecosystem NEE are less clear. We found that climate anomalies affect the IAV of NEE primarily through their differential impacts on ecosystem C uptake and respiration. Moreover, recent studies suggest that the carbon uptake period makes less contribution than the carbon uptake amplitude to IAV in NEE. Although land models incorporate most processes underlying IAV, their efficacy to predict the IAV in NEE remains low. Main conclusions To improve our ability to predict future IAV of the terrestrial C cycle, we have to understand biological mechanisms through which anomalies in climate factors cause the IAV of NEE. Future research needs to pay more attention not only to the differential effects of climate anomalies on photosynthesis and respiration but also to the relative importance of the C uptake period and amplitude in causing the IAV of NEE. Ultimately, we need multiple independent approaches, such as benchmark analysis, data assimilation and time‐series statistics, to integrate data, modelling frameworks and theory to improve our ability to predict future IAV in the terrestrial C cycle.

Transgenic Mice Overexpressing the Divalent Metal Transporter 1 Exhibit Iron Accumulation and Enhanced Parkin Expression in the Brain - Cheng-Wu Zhang; Yee Kit Tai; Bing-Han Chai; Katherine C. M. Chew; Eng-Tat Ang; Fai Tsang; Bryce W. Q. Tan; Eugenia T. E. Hong; Abu Bakar Ali Asad; Kai-Hsiang Chuang; Kah-Leong Lim; Tuck Wah Soong (NeuroMolecular Medicine, 2017)

Identifying functional groups and ecological roles of tropical and subtropical freshwater Cladocera in Asia - Eric Zeus C. Rizo; Yangliang Gu; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2017)

Cerebellar Pathology in Familial vs. Sporadic Essential Tremor - Elan D. Louis; Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2017)

Phosphodiesterase-5 inhibitors and their analogues as adulterants of herbal and food products: analysis of the Malaysian market, 2014–16 - Nur Baizura Bujang; Chin Fei Chee; Choon Han Heh; Noorsaadah Abd. Rahman; Michael J. C. Buckle (Food Additives & Contaminants: Part A, 2017)

Magnetically recoverable TiO2-WO3 photocatalyst to oxidize bisphenol A from model wastewater under simulated solar light - S. Dominguez; M. Huebra; C. Han; P. Campo; M.N. Nadagouda; M.J. Rivero; I. Ortiz; D. D. Dionysiou (Environmental Science and Pollution Research, 2017)

Variability of the Pacific North Equatorial Current and its implications on Japanese eel ( Anguilla japonica ) larval migration - Ango C. Hsu; Huijie Xue; Fei Chai; Peng Xiu; Yu‐San Han (Fisheries Oceanography, 2017)
The zonal velocity produced by a Regional Ocean Modeling System ( ROMS )‐based Pacific Ocean circulation model was validated against in situ measurements along the 137°E longitude. The Pacific model successfully reproduced the position and the shape of the North Equatorial Current ( NEC ) as well as the latitude of maximum surface velocity in the NEC region (8–17°N). The flow field produced by the Pacific model was then used to conduct numerical Lagrangian experiments, in which passive particles were released along a transect (142.5°E, 12.5–17°N) that traverses the known Japanese eel spawning area, and the effects of NEC strength and bifurcation latitude on the particle advection in the northwest Pacific were studied. Our results suggest that, in the 20‐yr period (1993–2012), the variability of the currents alone can cause interannual variability of one order of magnitude in the Kuroshio Entrance ( KE ), the percentage of particles entering the Kuroshio, the range of which varies from 43% in 1997 to 6% in 2012. The yearly‐averaged KE is not sensitive to the NEC bifurcation latitude. Instead, it is controlled by the average zonal velocity of a fixed domain (125–143°E, 13.5–17°N) and related to a recently‐developed climate index, the Philippines–Taiwan Oscillation ( PTO ). During the positive phase of the PTO , the zonal velocity in the domain, hence the yearly‐averaged KE, increases, and the opposite is true in the negative phase of the PTO. Considering only the trajectories, diel vertical migrations ( DVM ) in the top 400 m do not significantly affect Japanese eel larval transport, as incorporating DVM schemes does not increase the KE .

Cerebellar Pathology in Early Onset and Late Onset Essential Tremor - Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Elan D. Louis; Phyllis L. Faust (The Cerebellum, 2017)

IGF-1 has sexually dimorphic, pleiotropic, and time-dependent effects on healthspan, pathology, and lifespan - Nicole M. Ashpole; Sreemathi Logan; Andriy Yabluchanskiy; Matthew C. Mitschelen; Han Yan; Julie A. Farley; Erik L. Hodges; Zoltan Ungvari; Anna Csiszar; Sixia Chen; Constantin Georgescu; Gene B. Hubbard; et al. (GeroScience, 2017)

The Next Decade of Big Data in Ecosystem Science - S. L. LaDeau; B. A. Han; E. J. Rosi-Marshall; K. C. Weathers (Ecosystems, 2017)

Mapping Purkinje Cell Placement Along the Purkinje Cell Layer: an Analysis of Postmortem Tissue from Essential Tremor Patients vs. Controls - Elan D. Louis; Daniel Rabinowitz; Matthew Choe; William J. Tate; Geoffrey C. Kelly; Sheng-Han Kuo; Phyllis L. Faust (The Cerebellum, 2016)

Assessing the impacts of sea-level rise and precipitation change on the surficial aquifer in the low-lying coastal alluvial plains and barrier islands, east-central Florida (USA) - Han Xiao; Dingbao Wang; Scott C. Hagen; Stephen C. Medeiros; Carlton R. Hall (Hydrogeology Journal, 2016)

Response of herbivore functional groups to sequential perturbations in Moorea, French Polynesia - Xueying Han; Thomas C. Adam; Russell J. Schmitt; Andrew J. Brooks; Sally J. Holbrook (Coral Reefs, 2016)

Synthesis and accumulation of glutenin subunits during grain development in bread wheat as revealed by reversed-phase ultra-performance liquid chromatography (RP-UPLC) - J. Zhou; W. Liu; C. Han; H. Cao; Y. Xu; W. Zhang; Y. Yan (Cereal Research Communications, 2016)

An atypical 12q24.31 microdeletion implicates six genes including a histone demethylase KDM2B and a histone methyltransferase SETD1B in syndromic intellectual disability - Jonathan D. J. Labonne; Kang-Han Lee; Shigeki Iwase; Il-Keun Kong; Michael P. Diamond; Lawrence C. Layman; Cheol-Hee Kim; Hyung-Goo Kim (Human Genetics, 2016)

Keeping house: evaluation of housekeeping genes for real-time PCR in the red alga, Bostrychia moritziana (Florideophyceae) - Junbo Shim; Eunyoung Shim; Gwang Hoon Kim; Jong Won Han; Giuseppe C. Zuccarello (Algae, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

Biocontrol potential of antagonist Bacillus subtilis Tpb55 against tobacco black shank - T. Han; C. You; L. Zhang; C. Feng; C. Zhang; J. Wang; F. Kong (BioControl, 2016)

Exercise protects against PCB-induced inflammation and associated cardiovascular risk factors - Margaret O. Murphy; Michael C. Petriello; Sung Gu Han; Manjula Sunkara; Andrew J. Morris; Karyn Esser; Bernhard Hennig (Environmental Science and Pollution Research, 2016)

Nutrient resorption helps drive intra-specific coupling of foliar nitrogen and phosphorus under nutrient-enriched conditions - Xiao-Tao Lü; Sasha C. Reed; Qiang Yu; Xing-Guo Han (Plant and Soil, 2016)

Efficacy of oral moxifloxacin for aerobic vaginitis - C. Wang; C. Han; N. Geng; A. Fan; Y. Wang; Y. Yue; H. Zhang; F. Xue (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Cognition and Depression Following Deep Brain Stimulation of the Subthalamic Nucleus and Globus Pallidus Pars Internus in Parkinson’s Disease: A Meta-Analysis - Hannah L. Combs; Bradley S. Folley; David T. R. Berry; Suzanne C. Segerstrom; Dong Y. Han; Amelia J. Anderson-Mooney; Brittany D. Walls; Craig van Horne (Neuropsychology Review, 2015)

Tuna and swordfish catch in the U.S. northwest Atlantic longline fishery in relation to mesoscale eddies - Ango C. Hsu; Andre M. Boustany; Jason J. Roberts; Jui‐Han Chang; Patrick N. Halpin (Fisheries Oceanography, 2015)

Evaluation and application of cryosectioning in undecalcified hard tissues in cartilage and bone regenerative medicine - Seung Hwa Park; Jeewon Yoon; Jae Hyun Park; Bo Young Kim; Judee Grace E. Nemeno; Ernesto C. Balolong; Yuna Han; Kyung Mi Lee; Soojung Lee; Jeong Ik Lee (Tissue Engineering and Regenerative Medicine, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

Erratum to: Mutations of HNRNPA0 and WIF1 predispose members of a large family to multiple cancers - Chongjuan Wei; Bo Peng; Younghun Han; Wei V. Chen; Joshua Rother; Gail E. Tomlinson; C. Richard Boland; Damien Chaussabel; Marsha L. Frazier; Christopher I. Amos (Familial Cancer, 2015)

Mutations of HNRNPA0 and WIF1 predispose members of a large family to multiple cancers - Chongjuan Wei; Bo Peng; Younghun Han; Wei V. Chen; Joshua Rother; Gail E. Tomlinson; C. Richard Boland; Marc Chaussabel; Marsha L. Frazier; Christopher I. Amos (Familial Cancer, 2015)

Sensitivity of Alternaria solani to boscalid and control of boscalid resistance with commonly-used fungicides in Shanxi, China - X. J. Shi; L. Ren; Y. Q. Song; J. C. Han; H. P. Liu; Y. J. Zhang (Australasian Plant Pathology, 2015)

Modeling groundwater quality over a humid subtropical region using numerical indices, earth observation datasets, and X-ray diffraction technique: a case study of Allahabad district, India - Sudhir Kumar Singh; Prashant K. Srivastava; Dharmveer Singh; Dawei Han; Sandeep Kumar Gautam; A. C. Pandey (Environmental Geochemistry and Health, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Occurrence and distribution of phthalate esters and pharmaceuticals in Taiwan river sediments - Gordon C. C. Yang; Chih-Lung Wang; Yu-Han Chiu (Journal of Soils and Sediments, 2015)

Evaluating the causal basis of ecological success within the scleractinia: an integral projection model approach - Peter J. Edmunds; Scott C. Burgess; Hollie M. Putnam; Marissa L. Baskett; Lorenzo Bramanti; Nick S. Fabina; Xueying Han; Michael P. Lesser; Joshua S. Madin; Christopher B. Wall; Denise M. Yost; Ruth D. Gates (Marine Biology, 2014)

Differential Aortic and Mitral Valve Interstitial Cell Mineralization and the Induction of Mineralization by Lysophosphatidylcholine In Vitro - Dena C. Wiltz; Richard I. Han; Reid L. Wilson; Aditya Kumar; Joel D. Morrisett; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2014)

Trajectory of overall health from self-report and factors contributing to health declines among cancer survivors - Jessica L. Petrick; Randi E. Foraker; Anna M. Kucharska-Newton; Bryce B. Reeve; Elizabeth A. Platz; Sally C. Stearns; Xuesong Han; B. Gwen Windham; Debra E. Irwin (Cancer Causes & Control, 2014)

Diagnosis of the marine low cloud simulation in the NCAR community earth system model (CESM) and the NCEP global forecast system (GFS)-modular ocean model v4 (MOM4) coupled model - Heng Xiao; C. Roberto Mechoso; Ruiyu Sun; Jongil Han; Hua-Lu Pan; Sungsu Park; Cecile Hannay; Chris Bretherton; Joao Teixeira (Climate Dynamics, 2014)

Voices of Multi-ethnic Providers in NYC: Health Care for Viral Hepatitis to Prevent Hepatocellular Carcinoma - Hyosun Han; Ponni V. Perumalswami; Lawrence C. Kleinman; Lina H. Jandorf (Journal of Cancer Education, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Trojan Genes or Transparent Genomes? Sexual Selection and Potential Impacts of Genetically Modified Animals in Natural Ecosystems - C. David Rollo; Aarti Kumar; Richard Smith; Jiaxi Wang; Vadim Aksenov; Jiawei Han; Parul Khanna (Evolutionary Biology, 2014)

Association of prohibitin-1 and 2 with oxidative stress in rats with renal interstitial fibrosis - Tian-Biao Zhou; Yuan-Han Qin; Feng-Ying Lei; Wei-Fang Huang; Gregor P. C. Drummen (Molecular Biology Reports, 2014)

LIM homeobox transcription factor 1B is associated with pro-fibrotic components and apoptosis in hypoxia/reoxygenation renal tubular epithelial cells - Tian-Biao Zhou; Hui-Ling Xu; Yuan-Han Qin; Feng-Ying Lei; Wei-Fang Huang; Gregor P. C. Drummen (Apoptosis, 2014)

Cellular mechanisms in intermittent hypoxia-induced cardiac damage in vivo - Qian Han; Sze C. Yeung; Mary S. M. Ip; Judith C. W. Mak (Journal of Physiology and Biochemistry, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

CXCR4 pathway associated with family history of melanoma - Wen-Qing Li; Jiali Han; Hans R. Widlund; Mick Correll; Yaoyu E. Wang; John Quackenbush; Martin C. Mihm; Alvaro Laga Canales; Shaowei Wu; Todd Golub; Yujin Hoshida; David J. Hunter; et al. (Cancer Causes & Control, 2014)

Applications of capillary electrophoresis for rapidly separating and characterizing water-soluble proteins of wheat grains - C. Han; Z. Yu; S. Feng; D. Lv; X. Yan; G. Chen; X. Li; W. Ma; Y. Yan (Cereal Research Communications, 2013)

Challenge of weed risk assessment (WRA) for ecological restoration in China: The case of Rhus typhina L. and the new officially released weed risk assessment system - G. M. Wang; J. C. Yang; C. D. Jiang; G. M. Jiang; J. B. Yu; H. B. Shao; G. X. Han; Y. J. Gao (Plant Biosystems, 2013)

Effects of total replacement of dietary fish oil on growth performance and fatty acid compositions of hybrid tilapia (Oreochromis niloticus × O. aureus) - C.-Y. Han; Q.-M. Zheng; L.-N. Feng (Aquaculture International, 2013)

Differential gene expression in human hepatocyte cell lines exposed to the antiretroviral agent zidovudine - Jia-Long Fang; Tao Han; Qiangen Wu; Frederick A. Beland; Ching-Wei Chang; Lei Guo; James C. Fuscoe (Archives of Toxicology, 2013)

Population Pharmacokinetics of Cyclosporine in Transplant Recipients - Kelong Han; Venkateswaran C. Pillai; Raman Venkataramanan (The AAPS Journal, 2013)

β-Ionone arrests cell cycle of gastric carcinoma cancer cells by a MAPK pathway - Hong-Wei Dong; Shuang Zhang; Wen-Guang Sun; Qian Liu; Juan C. Ibla; Sulpicio G. Soriano; Xiao-Hui Han; Lian-Xin Liu; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Experimental study of hollow rectangular bridge column performance under vertical and cyclically bilateral loads - Qiang Han; Xiuli Du; Yihui Zhou; George C. Lee (Earthquake Engineering and Engineering Vibration, 2013)

Erratum to: Accumulation of galloyl derivatives in a green alga, Spirogyra varians, in response to cold stress - Jong Won Han; Minchul Yoon; Frithjof C. Küpper; Tatyana A. Klochkova; Jung-Soon Oh; Jung-Rae Rho; Gwang Hoon Kim (Journal of Applied Phycology, 2013)

Heterogeneity in the mycelium: implications for the use of fungi as cell factories - Han A. B. Wösten; G. Jerre van Veluw; C. de Bekker; Pauline Krijgsheld (Biotechnology Letters, 2013)

Whole exome sequencing in dominant cataract identifies a new causative factor, CRYBA2, and a variety of novel alleles in known genes - Linda M. Reis; Rebecca C. Tyler; Sanaa Muheisen; Victor Raggio; Leonardo Salviati; Dennis P. Han; Deborah Costakos; Hagith Yonath; Sarah Hall; Patricia Power; Elena V. Semina (Human Genetics, 2013)

Characterization of the root-predominant gene promoter HPX1 in transgenic rice plants - Su-Hyun Park; Jin Seo Jeong; Eun Hyang Han; Mark C. F. R. Redillas; Seung Woon Bang; Harin Jung; Youn Shic Kim; Ju-Kon Kim (Plant Biotechnology Reports, 2013)

Improvement of short-term forecasting in the northwest Pacific through assimilating Argo data into initial fields - Hongli Fu; Peter C. Chu; Guijun Han; Zhongjie He; Wei Li; Xuefeng Zhang (Acta Oceanologica Sinica, 2013)

Pathogenesis of type 1 (European genotype) porcine reproductive and respiratory syndrome virus in male gonads of infected boar - K. Han; H. W. Seo; Y. Oh; I. Kang; C. Park; J. H. Han; S.-H. Kim; C. Chae (Veterinary Research Communications, 2013)

Photocatalytic degradation of contaminants of concern with composite NF-TiO2 films under visible and solar light - H. Barndõk; M. Peláez; C. Han; W. E. Platten; P. Campo; D. Hermosilla; A. Blanco; D. D. Dionysiou (Environmental Science and Pollution Research, 2013)

Evaluation of organic contamination in urban groundwater surrounding a municipal landfill, Zhoukou, China - D. M. Han; X. X. Tong; M. G. Jin; Emily Hepburn; C. S. Tong; X. F. Song (Environmental Monitoring and Assessment, 2013)

Apoptosis initiation of β-ionone in SGC-7901 gastric carcinoma cancer cells via a PI3K-AKT pathway - Qian Liu; Hong-Wei Dong; Wen-Guang Sun; Ming Liu; Juan C. Ibla; Lian-Xin Liu; John W. Parry; Xiao-Hui Han; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Absence of induced resistance in Agaricus bisporus against Lecanicillium fungicola - Roeland L. Berendsen; Niek Schrier; Stefanie I. C. Kalkhove; Luis G. Lugones; Johan J. P. Baars; Carolien Zijlstra; Marjanne de Weerdt; Han A. B. Wösten; Peter A. H. M. Bakker (Antonie van Leeuwenhoek, 2013)

Effect of cholesterol on lipogenesis and VLDL–TG assembly and secretion in goose primary hepatocytes - C. C. Han; J. W. Wang; Z. X. Pan; H. Tang; S. X. Xiang; J. Wang; L. Li; F. Xu; S. H. Wei (Molecular and Cellular Biochemistry, 2013)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Isolation and Characterization of a Lytic Myoviridae Bacteriophage PAS-1 with Broad Infectivity in Aeromonas salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; D. H. Kang; C. Oh; S. J. Heo; S. C. Park (Current Microbiology, 2012)

Nest-Building by Chimpanzees (Pan troglodytes verus) at Seringbara, Nimba Mountains: Antipredation, Thermoregulation, and Antivector Hypotheses - Kathelijne Koops; William C. McGrew; Han de Vries; Tetsuro Matsuzawa (International Journal of Primatology, 2012)

Integrating pathway analysis and genetics of gene expression for genome-wide association study of basal cell carcinoma - Mingfeng Zhang; Liming Liang; Nilesh Morar; Anna L. Dixon; G. Mark Lathrop; Jun Ding; Miriam F. Moffatt; William O. C. Cookson; Peter Kraft; Abrar A. Qureshi; Jiali Han (Human Genetics, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Complete genomic sequence of a T4-like bacteriophage, phiAS4, infecting Aeromonas salmonicida subsp. salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Genomic sequence of infectious hypodermal and hematopoietic necrosis virus (IHHNV) KLV-2010-01 originating from the first Korean outbreak in cultured Litopenaeus vannamei - J. H. Kim; H. K. Kim; V. G. Nguyen; B. K. Park; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Prevalence and different characteristics of two serotypes of Streptococcus parauberis isolated from the farmed olive flounder, Paralichthys olivaceus (Temminck and Schlegel), in Korea - S Y Han; B K Kang; B J Kang; S P Shin; B H Soen; J M Kim; J H Kim; C H Choresca; J E Han; J W Jun; S C Park (Journal of Fish Diseases, 2011)
The prevalence of two serotypes of Streptococcus parauberis isolated from the olive flounder, Paralichthys olivaceus , was evaluated in a total of 29 isolates between 2003 and 2010 in Korea. Streptococcus parauberis isolates were divided into two serologically distinct types (serotype 1 and serotype 2), except for one strain (S1091), using an agglutination assay with rabbit antiserum, and serotype 1 was identified as the dominant type (24 of 29 isolates) in this study. To identify the characteristics of the two serotypes of S. parauberis , we conducted a biochemical test using the API 20 Strep kit, a transmission electron microscopy (TEM) assay, sequence analysis of 16S‐23S rRNA intergenic spacer region (ISR) and a pathogenicity test. In TEM, both serotypes possessed polysaccharide capsule layers around the cell surface when bacterial cells were treated with a homologous serotype of rabbit antiserum. However, we were unable to discriminate serotype‐specific biochemical characteristics and genetic characteristics of 16S‐23S rRNA ISR between the two serotypes. In the pathogenicity test, the serotype 1 strains induced significantly higher mortality than the serotype 2 strains in olive flounder when experimentally inoculated via the intraperitoneal route.

AAPS Workshop Report: Strategies to Address Therapeutic Protein–Drug Interactions during Clinical Development - Sandhya Girish; Steven W Martin; Mark C Peterson; Lei K. Zhang; Hong Zhao; Joseph Balthasar; Raymond Evers; Honghui Zhou; Min Zhu; Lewis Klunk; Chao Han; Eva Gil Berglund; et al. (The AAPS Journal, 2011)

Structural evolution of the northern East China Sea Shelf Basin interpreted from cross-section restoration - Deniz Cukur; Senay Horozal; Gwang H. Lee; Dae C. Kim; Hyun C. Han; Moo H. Kang (Marine Geophysical Research, 2011)

Application of EM algorithms for seismic facices classification - Mei Han; Yong Zhao; Gaoming Li; Albert C. Reynolds (Computational Geosciences, 2011)

Anti-inflammatory/Anti-oxidative Stress Activities and Differential Regulation of Nrf2-Mediated Genes by Non-Polar Fractions of Tea Chrysanthemum zawadskii and Licorice Glycyrrhiza uralensis - Tien-Yuan Wu; Tin Oo Khor; Constance Lay Lay Saw; Stephanie C. Loh; Alvin I. Chen; Soon Sung Lim; Jung Han Yoon Park; Li Cai; Ah-Ng Tony Kong (The AAPS Journal, 2011)

Atypical Aeromonas salmonicida infection in the black rockfish, Sebastes schlegeli Hilgendorf , in Korea - H‐J Han; D‐Y Kim; W‐S Kim; C‐S Kim; S‐J Jung; M‐J Oh; D‐H Kim (Journal of Fish Diseases, 2011)
Cultured black rockfish, Sebastes schlegeli , suffered mass mortalities during winter 2008 and spring 2009 in Korea, showing clinical signs of ulcer lesions and haemorrhages over their body surface. The aetiological agent was identified as Aeromonas salmonicida (strains RFAS‐1, ‐2 and ‐3), which is a non‐pigmented, slow‐growing bacterium. Phenotypes of RFAS strains showed variation, while 16S rRNA, gyrB , rpoD , dnaJ and recA gene sequences of all the strains were affiliated to A. salmonicida. In particular, vapA gene sequences of the strains were most closely related to one of the five subspecies of A. salmonicida subsp. masoucida (=KCCM 40239 T ). LD 50 values of RFAS‐1 for intraperitoneal and intramuscular injection were 1.5 × 10 5.25 and 1.5 × 10 6.4 cfu/rockfish, respectively. However, A. salmonicida strains KCCM 40239 T and SAS‐1, which originate from masou and chum salmon, respectively, were not pathogenic to black rockfish. RFAS strains, possessing A‐layer protein on their surface, exhibited β‐haemolytic activity against rockfish erythrocytes and capability to survive in rockfish serum, which seem to be associated with virulence.

A Matched Asymptotic Expansion Analysis of Highly Unsteady Porous Media Flows - S. Y. Han; D. Hansen; G. C. Kember (Transport in Porous Media, 2010)

The distribution and characteristics of the igneous complexes in the northern East China Sea Shelf Basin and their implications for hydrocarbon potential - Deniz Cukur; Senay Horozal; Dae C. Kim; Gwang H. Lee; Hyun C. Han; Moo H. Kang (Marine Geophysical Research, 2010)

Leaf habit and woodiness regulate different leaf economy traits at a given nutrient supply - Jenny C. Ordoñez; Peter M. van Bodegom; Jan-Philip M. Witte; Ruud P. Bartholomeus; Han F. van Dobben; Rien Aerts (Ecology, 2010)
The large variation in the relationships between environmental factors and plant traits observed in natural communities exemplifies the alternative solutions that plants have developed in response to the same environmental limitations. Qualitative attributes, such as growth form, woodiness, and leaf habit can be used to approximate these alternative solutions. Here, we quantified the extent to which these attributes affect leaf trait values at a given resource supply level, using measured plant traits from 105 different species (254 observations) distributed across 50 sites in mesic to wet plant communities in The Netherlands. For each site, soil total N, soil total P, and water supply estimates were obtained by field measurements and modeling. Effects of growth forms, woodiness, and leaf habit on relations between leaf traits (SLA, specific leaf area; LNC, leaf nitrogen concentration; and LPC, leaf phosphorus concentration) vs. nutrient and water supply were quantified using maximum‐likelihood methods and Bonferroni post hoc tests. The qualitative attributes explained 8–23% of the variance within sites in leaf traits vs. soil fertility relationships, and therefore they can potentially be used to make better predictions of global patterns of leaf traits in relation to nutrient supply. However, at a given soil fertility, the strength of the effect of each qualitative attribute was not the same for all leaf traits. These differences may imply a differential regulation of the leaf economy traits at a given nutrient supply, in which SLA and LPC seem to be regulated in accordance to changes in plant size and architecture while LNC seems to be primarily regulated at the leaf level by factors related to leaf longevity.

The genome of the Gram‐positive metal‐ and sulfate‐reducing bacterium Desulfotomaculum reducens strain MI‐1 - Pilar Junier; Thomas Junier; Sheila Podell; David R. Sims; John C. Detter; Athanasios Lykidis; Cliff S. Han; Nicholas S. Wigginton; Terry Gaasterland; Rizlan Bernier‐Latmani (Environmental Microbiology, 2010)
Summary Spore‐forming, Gram‐positive sulfate‐reducing bacteria (SRB) represent a group of SRB that dominates the deep subsurface as well as niches in which resistance to oxygen and dessication is an advantage. Desulfotomaculum reducens strain MI‐1 is one of the few cultured representatives of that group with a complete genome sequence available. The metabolic versatility of this organism is reflected in the presence of genes encoding for the oxidation of various electron donors, including three‐ and four‐carbon fatty acids and alcohols. Synteny in genes involved in sulfate reduction across all four sequenced Gram‐positive SRB suggests a distinct sulfate‐reduction mechanism for this group of bacteria. Based on the genomic information obtained for sulfate reduction in D. reducens , the transfer of electrons to the sulfite and APS reductases is proposed to take place via the quinone pool and heterodisulfide reductases respectively. In addition, both H 2 ‐evolving and H 2 ‐consuming cytoplasmic hydrogenases were identified in the genome, pointing to potential cytoplasmic H 2 cycling in the bacterium. The mechanism of metal reduction remains unknown.

Master donor viruses A/Leningrad/134/17/57 (H2N2) and B/USSR/60/69 and derived reassortants used in live attenuated influenza vaccine (LAIV) do not display neurovirulent properties in a mouse model - J. Theo M. Voeten; Irina V. Kiseleva; Harrie L. Glansbeek; Stephanie M. C. Basten; Sandra K. M. Drieszen-van der Cruijsen; Larisa G. Rudenko; Han van den Bosch; Jacco G. M. Heldens (Archives of Virology, 2010)

Evaluation of Ocean Tide Models Used for Jason-2 Altimetry Corrections - H. S. Fok; H. Baki Iz; C. K. Shum; Yuchan Yi; Ole Andersen; Alexander Braun; Yi Chao; Guoqi Han; C. Y. Kuo; Koji Matsumoto; Y. Tony Song (Marine Geodesy, 2010)

Determination of Imazaquin and its Metabolite by Liquid Chromatography-Quadrupole-Time of Flight Tandem Mass - H. B. Yao; G. J. Han; G. X. Liu; Y. Xie; C. H. Wang (Bulletin of Environmental Contamination and Toxicology, 2010)

Does larval duration contribute to population genetic isolation of the Japanese eel Anguilla japonica ? - Y. S. HAN; C. L. HUNG; Y. IIZUKA; H. C. CHANG; B. J. CHANG; H. C. HO; J. C. SHIAO (Fisheries Management and Ecology, 2010)

Human Enteric Viruses in Groundwater - S. H. Park; E. J. Kim; T. H. Yun; J. H. Lee; C. K. Kim; Y. H. Seo; S. A. Oh; S. S. Choi; S. J. Cho; M. S. Kim; G. Y. Han; M. Y. Kim; et al. (Food and Environmental Virology, 2010)

Landscape‐scale analyses suggest both nutrient and antipredator advantages to Serengeti herbivore hotspots - T. Michael Anderson; J. Grant C. Hopcraft; Stephanie Eby; Mark Ritchie; James B. Grace; Han Olff (Ecology, 2010)
Mechanistic explanations of herbivore spatial distribution have focused largely on either resource‐related (bottom‐up) or predation‐related (top‐down) factors. We studied direct and indirect influences on the spatial distributions of Serengeti herbivore hotspots, defined as temporally stable areas inhabited by mixed herds of resident grazers. Remote sensing and variation in landscape features were first used to create a map of the spatial distribution of hotspots, which was tested for accuracy against an independent data set of herbivore observations. Subsequently, we applied structural equation modeling to data on soil fertility and plant quality and quantity across a range of sites. We found that hotspots in Serengeti occur in areas that are relatively flat and located away from rivers, sites where ungulates are less susceptible to predation. Further, hotspots tend to occur in areas where hydrology and rainfall create conditions of relatively low‐standing plant biomass, which, coupled with grazing, increases forage quality while decreasing predation risk. Low‐standing biomass and higher leaf concentrations of N, Na, and Mg were strong direct predictors of hotspot occurrence. Soil fertility had indirect effects on hotspot occurrence by promoting leaf Na and Mg. The results indicate that landscape features contribute in direct and indirect ways to influence the spatial distribution of hotspots and that the best models incorporated both resource‐ and predation‐related factors. Our study highlights the collective and simultaneous role of bottom‐up and top‐down factors in determining ungulate spatial distributions.

Changes in the frequency, scale, and failing areas of latest Quaternary (<29.4 cal. ka B.P.) slope failures along the SW Ulleung Basin, East Sea (Japan Sea), inferred from depositional characters of densely dated turbidite successions - Sang Hoon Lee; Jang J. Bahk; Han J. Kim; Kyung E. Lee; Hyeong T. Jou; Bong C. Suk (Geo-Marine Letters, 2010)

Internal reflection pattern of Korea Strait shelf mud (Nakdong River subaqueous delta) off southeast Korea and implications for Holocene relative base‐level change - Gwang H. Lee; Dae C. Kim; Mi K. Park; Soo C. Park; Han J. Kim; Hyeong T. Jou; Boo K. Khim (Island Arc, 2010)
The Korea Strait shelf mud (KSSM) (Nakdong River subaqueous delta) is the most conspicuous Holocene sedimentary feature in the inner shelf off southeast Korea. Analysis of multi‐channel sparker profiles and 14 C ages of sediment cores reveals that the KSSM consists of three seismic units at the depocenter (>60 m thick): (i) the thin transgressive bottom (> ca 8000 cal bp ); (ii) thick (>40 m) obliquely progradational middle ( ca 8000– ca 2600 cal bp ); and (iii) thin transgressive top ( ca 2600 cal bp –present) units. The relative base level, predicted from the internal reflection pattern of the KSSM, remained significantly deeper (up to >70 m) than global sealevel during much of the Holocene. The apparent gradual drop (∼20 m) of the relative base level during the deposition of the middle unit, followed by a rise, further suggests that base level does not conform to sealevel and is more sensitive than the relative sealevel is to the local oceanographic regime and processes.

Application of an Improved Flow-Stress-Damage Model to the Criticality Assessment of Water Inrush in a Mine: a Case Study - H. Q. Zhang; Y. N. He; C. A. Tang; Bashir Ahmad; L. J. Han (Rock Mechanics and Rock Engineering, 2009)

Prothoracic Gland Semiochemicals of Green Lacewings - Jeffrey Richard Aldrich; Thanh C. Le; Qing-He Zhang; Jorge Torres; Shaun L. Winterton; Baoyu Han; Gary L. Miller; Kamlesh R. Chauhan (Journal of Chemical Ecology, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

Comments on “Abrupt-Interface Solution for Carbon dioxide Injection into Porous Media” by M. Dentz and D. Tartakovsky - Chuan Lu; Si-Yong Lee; Weon Shik Han; Brain J. McPherson; Peter C. Lichtner (Transport in Porous Media, 2009)

Bacteria beneath the West Antarctic Ice Sheet - Brian Lanoil; Mark Skidmore; John C. Priscu; Sukkyun Han; Wilson Foo; Stefan W. Vogel; Slawek Tulaczyk; Hermann Engelhardt (Environmental Microbiology, 2009)
Summary Subglacial environments, particularly those that lie beneath polar ice sheets, are beginning to be recognized as an important part of Earth's biosphere. However, except for indirect indications of microbial assemblages in subglacial Lake Vostok, Antarctica, no sub‐ice sheet environments have been shown to support microbial ecosystems. Here we report 16S rRNA gene and isolate diversity in sediments collected from beneath the Kamb Ice Stream, West Antarctic Ice Sheet and stored for 15 months at 4°C. This is the first report of microbes in samples from the sediment environment beneath the Antarctic Ice Sheet. The cells were abundant (∼10 7 cells g −1 ) but displayed low diversity (only five phylotypes), likely as a result of enrichment during storage. Isolates were cold tolerant and the 16S rRNA gene diversity was a simplified version of that found in subglacial alpine and Arctic sediments and water. Although in situ cell abundance and the extent of wet sediments beneath the Antarctic ice sheet can only be roughly extrapolated on the basis of this sample, it is clear that the subglacial ecosystem contains a significant and previously unrecognized pool of microbial cells and associated organic carbon that could potentially have significant implications for global geochemical processes.

Detection of Autoinducer-2 and Analysis of the Profile of luxS and pfs Transcription in Streptococcus suis Serotype 2 - X. G. Han; C. P. Lu (Current Microbiology, 2009)

Estimation of the gross primary production of an old‐growth temperate mixed forest using eddy covariance and remote sensing - J. B. Wu; X. M. Xiao; D. X. Guan; T. T. Shi; C. J. Jin; S. J. Han (International Journal of Remote Sensing, 2009)

Ivermectin inhibits LPS-induced production of inflammatory cytokines and improves LPS-induced survival in mice - X. Zhang; Y. Song; X. Ci; N. An; Y. Ju; H. Li; X. Wang; C. Han; J. Cui; X. Deng (Inflammation Research, 2008)

The complete genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ) - Elizabeth Pierce; Gary Xie; Ravi D. Barabote; Elizabeth Saunders; Cliff S. Han; John C. Detter; Paul Richardson; Thomas S. Brettin; Amaresh Das; Lars G. Ljungdahl; Stephen W. Ragsdale (Environmental Microbiology, 2008)
Summary This paper describes the genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ), which is the model acetogenic bacterium that has been widely used for elucidating the Wood–Ljungdahl pathway of CO and CO 2 fixation. This pathway, which is also known as the reductive acetyl‐CoA pathway, allows acetogenic (often called homoacetogenic) bacteria to convert glucose stoichiometrically into 3 mol of acetate and to grow autotrophically using H 2 and CO as electron donors and CO 2 as an electron acceptor. Methanogenic archaea use this pathway in reverse to grow by converting acetate into methane and CO 2 . Acetogenic bacteria also couple the Wood–Ljungdahl pathway to a variety of other pathways to allow the metabolism of a wide variety of carbon sources and electron donors (sugars, carboxylic acids, alcohols and aromatic compounds) and electron acceptors (CO 2 , nitrate, nitrite, thiosulfate, dimethylsulfoxide and aromatic carboxyl groups). The genome consists of a single circular 2 628 784 bp chromosome encoding 2615 open reading frames (ORFs), which includes 2523 predicted protein‐encoding genes. Of these, 1834 genes (70.13%) have been assigned tentative functions, 665 (25.43%) matched genes of unknown function, and the remaining 24 (0.92%) had no database match. A total of 2384 (91.17%) of the ORFs in the M. thermoacetica genome can be grouped in orthologue clusters. This first genome sequence of an acetogenic bacterium provides important information related to how acetogens engage their extreme metabolic diversity by switching among different carbon substrates and electron donors/acceptors and how they conserve energy by anaerobic respiration. Our genome analysis indicates that the key genetic trait for homoacetogenesis is the core acs gene cluster of the Wood–Ljungdahl pathway.

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

Sources and Properties of Natural Organic Matter (NOM) in Water Along the Dongjiang River (the Source of Hong Kong’s Drinking Water) and Toxicological Assay of Its Chlorination By-Products - Y. Liang; H. C. Hong; L. H. Dong; C. Y. Lan; B. P. Han; M. H. Wong (Archives of Environmental Contamination and Toxicology, 2008)

Characterization of a Homogentisate Dioxygenase Mutant in Pseudomonas chlororaphis O6 - B. R. Kang; S. H. Han; S. M. Cho; A. J. Anderson; I. S. Kim; S. K. Park; Y. C. Kim (Current Microbiology, 2008)

A novel gene, Pi40(t), linked to the DNA markers derived from NBS-LRR motifs confers broad spectrum of blast resistance in rice - J. U. Jeung; B. R. Kim; Y. C. Cho; S. S. Han; H. P. Moon; Y. T. Lee; K. K. Jena (Theoretical and Applied Genetics, 2007)

Utilization of seagrass habitats by juvenile groupers and snappers in Banten Bay, Banten Province, Indonesia - Siti Nuraini; Eira C. Carballo; Wim L. T. van Densen; Marcel A. M. Machiels; Han J. Lindeboom; Leopold A. J. Nagelkerke (Hydrobiologia, 2007)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

Changes in phosphorus fractions, sorption and release in Udic Mollisols under different ecosystems - C. Song; X. Z. Han; C. Tang (Biology and Fertility of Soils, 2007)

Redirecting retroviral tropism by insertion of hepatitis B virus PreS1 core peptide into the envelope - P. Qi; J.-X. Han; Y.-Q. Lu; C.-X. Wang (Archives of Virology, 2007)

Gene expression profiling reveals two separate mechanisms regulating apoptosis in rectal carcinomas in vivo - Elza C. de Bruin; Simone van de Pas; Cornelis J. H. van de Velde; J. Han J. M. van Krieken; Lucy T. C. Peltenburg; Corrie A. M. Marijnen; Jan Paul Medema (Apoptosis, 2007)

Surveying sandy deserts and desertified lands in north‐western China by remote sensing - C. Z. Yan; T. Wang; Z. W. Han; Y. F. Qie (International Journal of Remote Sensing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Reusable immunomagnetic beads in an enzyme immunoassay - F. C. Han; J. Luo; H. F. Guo; W. H. Zhang; D. C. He; X. J. Yan (World Journal of Microbiology and Biotechnology, 2007)

Mammary tumor modifiers in BALB/cJ mice heterozygous for p53 - Joanna G. Koch; Xiangjun Gu; Younghun Han; Adel K. El-Naggar; Melissa V. Olson; Daniel Medina; D. Joseph Jerry; Anneke C. Blackburn; Gary Peltz; Christopher I. Amos; Guillermina Lozano (Mammalian Genome, 2007)

Plasma protein advanced glycation end products, carboxymethyl cysteine, and carboxyethyl cysteine, are elevated and related to nephropathy in patients with diabetes - Ahmed A. Mostafa; Edward W. Randell; Sudesh C. Vasdev; Vicki D. Gill; Yingchun Han; Vereesh Gadag; Ahmed A. Raouf; Hala El Said (Molecular and Cellular Biochemistry, 2007)

Importance of point sources on regional nitrous oxide fluxes in semi-arid steppe of Inner Mongolia, China - J. Holst; C. Liu; Z. Yao; N. Brüggemann; X. Zheng; X. Han; K. Butterbach-Bahl (Plant and Soil, 2007)

Estimating afternoon MODIS land surface temperatures (LST) based on morning MODIS overpass, location and elevation information - N. C. Coops; D. C. Duro; M. A. Wulder; T. Han (International Journal of Remote Sensing, 2007)

Distinct chromosomal distributions of highly repetitive sequences in maize - Jonathan C. Lamb; Julie M. Meyer; Blake Corcoran; Akio Kato; Fangpu Han; James A. Birchler (Chromosome Research, 2007)

Approaching chickpea quantitative trait loci conditioning resistance to Ascochyta rabiei via comparative genomics - X. Y. Bian; R. Ford; T. R. Han; T. E. Coram; E. C. K. Pang; P. W. J. Taylor (Australasian Plant Pathology, 2007)

Volume density and distribution of mitochondria in harbor seal (Phoca vitulina) skeletal muscle - Rebecca R. Watson; Shane B. Kanatous; Daniel F. Cowan; Julie W. Wen; Violet C. Han; Randall W. Davis (Journal of Comparative Physiology B, 2006)

Removal of Alachlor and Pretilachlor by Laboratory-Synthesized Zerovalent Iron in Pesticide Formulation Solution - H. Y. Kim; I. K. Kim; J. H. Shim; Y.-C. Kim; T.-H. Han; K.-C. Chung; P. I. Kim; B.-T. Oh; I. S. Kim (Bulletin of Environmental Contamination and Toxicology, 2006)

Pathogenicity of Edwardsiella tarda to olive flounder, Paralichthys olivaceus (Temminck & Schlegel) - H‐J Han; D‐H Kim; D‐C Lee; S‐M Kim; S‐I Park (Journal of Fish Diseases, 2006)
The LD 50 and cytotoxic and enzymatic activities of both cells and extracellular products (ECPs) of eight Edwardsiella tarda strains were determined and their bacterial superoxide dismutase gene (sodB) and catalase gene (katB) were sequenced. Strains were also examined for their ability to resist the immune responses of olive flounder, Paralichthys olivaceus . LD 50 values of strains (FSW910410, KE1, 2, 3, 4, 5 and 6) in olive flounder ranged between 10 2.5 and 10 5.3 cfu (colony forming units) per fish. Unlike the avirulent strain SU100 (LD 50 ≥ 10 7 ), all pathogenic strains were able to survive in flounder serum and head kidney leucocytes (except for KE2). The virulent strains possessed type I sodB and katB, whereas SU100 had type II sodB but not katB. However, there was no difference between avirulent and virulent strains in haemolytic and cytotoxic activities. The results of this study demonstrated that the ability of E. tarda to resist complement activity and phagocytosis is conferred by its superoxide dismutase and catalase, which thus play an essential role in the pathogenicity of this bacterium. In addition genotyping of sodB and kat B proved to be a very useful tool to distinguish virulent from avirulent strains.

Quantitation of Anaplasma marginale major surface protein (MSP)1a and MSP2 epitope-specific CD4+ T lymphocytes using bovine DRB3*1101 and DRB3*1201 tetramers - Junzo Norimine; Sushan Han; Wendy C. Brown (Immunogenetics, 2006)

Detection and identification of avian, duck, and goose reoviruses by RT-PCR: goose and duck reoviruses are part of the same genogroup in the genus Orthoreovirus - Y. Zhang; M. Liu; O. Shuidong; Q. L. Hu; D. C. Guo; H. Y. Chen; Z. Han (Archives of Virology, 2006)

Polysomes are associated with microtubules in fertilized eggs of Chinese pine (Pinus tabulaeformis) - Yuzhen Han; Jingjuan Yu; Fengli Guo; Simon C. Watkins (Protoplasma, 2006)

N-acetylphytosphingosine-induced apoptosis of Jurkat cells is mediated by the conformational change in Bak - Y. Han; Y. Kim; H. Kang; S. H. Hong; Y. H. Kim; D. -S. Lim; C. Park; Y. -S. Yun; J. -Y. Song (Apoptosis, 2006)

Pioglitazone, a synthetic ligand for PPARγ, induces apoptosis in RB-deficient human colorectal cancer cells - C. J. Lee; J. S. Han; C. Y. Seo; T. H. Park; H. C. Kwon; J. S. Jeong; I. H. Kim; J. Yun; Y. S. Bae; J. Y. Kwak; J. I. Park (Apoptosis, 2006)

Interactions Between High pH and Iron Supply on Nodulation and Iron Nutrition of Lupinus albus L. Genotypes Differing in Sensitivity to Iron Deficiency - C. Tang; S. J. Zheng; Y. F. Qiao; G. H. Wang; X. Z. Han (Plant and Soil, 2006)

Radon distribution in groundwater of Taiwan - Y. L. Han; M. C. Tom Kuo; K. C. Fan; C. J. Chiang; Y. P. Lee (Hydrogeology Journal, 2006)

Meprin β metalloprotease gene polymorphisms associated with diabetic nephropathy in the Pima Indians - Alexander R. Red Eagle; Robert L. Hanson; Weiping Jiang; Xiaoli Han; Gail L. Matters; Giuseppina Imperatore; William C. Knowler; Judith S. Bond (Human Genetics, 2005)

Novel Characteristics of Bifidobacterium bifidum in Solid State Fermentation System - Runlin Han; C. Edward Ebert; Zhihong Zhao; Liming Li; Heping Zhang; Ruihua Tian (World Journal of Microbiology and Biotechnology, 2005)

Interaction between the antidepressant-like behavioral effects of beta adrenergic agonists and the cyclic AMP PDE inhibitor rolipram in rats - Han-Ting Zhang; Ying Huang; Kathleen Mishler; Sandra C. Roerig; James M. O'Donnell (Psychopharmacology, 2005)

A Cryoinjury Model Using Engineered Tissue Equivalents for Cryosurgical Applications - Bumsoo Han; Erin D. Grassl; Victor H. Barocas; James E. Coad; John C. Bischof (Annals of Biomedical Engineering, 2005)

Phosphorus characteristics correlate with soil fertility of albic luvisols - X. Z. Han; C. Tang; C. Y. Song; S. Y. Wang; Y. F. Qiao (Plant and Soil, 2005)

Agrobacterium-mediated transformation of bottle gourd (Lagenaria siceraria Standl.) - J.-S. Han; C. K. Kim; S. H. Park; K. D. Hirschi; I.- G. Mok (Plant Cell Reports, 2005)

Characterization of an extracellular biopolymer flocculant from a haloalkalophilic Bacillus isolate - C. Ganesh Kumar; Han-seung Joo; Rajesh Kavali; Jang-won Choi; Chung-soon Chang (World Journal of Microbiology and Biotechnology, 2004)

Efficient plant regeneration from cotyledon explants of bottle gourd (Lagenaria siceraria Standl.) - J-S. Han; D-G. Oh; I-G. Mok; H-G. Park; C. K. Kim (Plant Cell Reports, 2004)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea - G. Yi; S.-K. Lee; Y.-K. Hong; Y.-C. Cho; M.-H. Nam; S.-C. Kim; S.-S. Han; G.-L. Wang; T.-R. Hahn; P.C. Ronald; J.-S. Jeon (Theoretical and Applied Genetics, 2004)

Bacterial enteritis and the development of the larval digestive tract in olive flounder, Paralichthys olivaceus (Temminck & Schlegel) - D‐H Kim; H‐J Han; S‐M Kim; D‐C Lee; S‐I Park (Journal of Fish Diseases, 2004)
Three bacterial isolates obtained from diseased olive flounder larvae, Paralichthys olivaceus , were identified as Vibrio ichthyoenteri based on the results of phenotypic characterization and 16S rRNA gene sequencing studies. Bacterial enteritis was reproduced in 16 and 22 days post‐hatch (dph) larvae by administering brine shrimp nauplii, Artemia salina , dosed with the environmental isolates and reference strains of V. ichthyoenteri . To investigate the effect of the disease on development of the stomach, a pepsin activity assay and reverse transcription‐polymerase chain reaction (RT‐PCR) analysis of the expression of the pepsinogen gene were performed. Expression of olive flounder pepsinogen was detected from 30‐dph larvae and the increased level of pepsin activity coincided with reduced susceptibility to the disease. Growth rates of V. ichthyoenteri , V. anguillarum and Edwardsiella tarda were tested in artificial stomach conditions using HCl and porcine pepsin. All the strains of V. ichthyoenteri were inhibited by low pH conditions which corresponded with an increase in pepsin levels. This suggests that differentiation of the stomach in olive flounder larvae and juveniles, an essential physiological development, also provides the host with a non‐immunological defence mechanism.

Penicillium persicinum, a new griseofulvin, chrysogine and roquefortine C producing species from Qinghai province, China - Long Wang; Han-Bai Zhou; Jens C. Frisvad; Robert A. Samson (Antonie van Leeuwenhoek, 2004)

Identification and molecular modelling of a mutation in the motor head domain of myosin VIIA in a family with autosomal dominant hearing impairment (DFNA11) - Mirjam W. J. Luijendijk; Erwin van Wijk; Anne M. L. C. Bischoff; Elmar Krieger; Patrick L. M. Huygen; Ronald J. E. Pennings; Han G. Brunner; Cor W. R. J. Cremers; Frans P. M. Cremers; Hannie Kremer (Human Genetics, 2004)

Thermostable Alkaline Protease from a Novel Marine Haloalkalophilic Bacillus Clausii Isolate - C. Ganesh Kumar; Han-Seung Joo; Yoon-Mo Koo; Seung R. Paik; Chung-Soon Chang (World Journal of Microbiology and Biotechnology, 2004)

Genotyping Possible Polymorphic Variants of Human Mismatch Repair Genes in Healthy Korean Individuals and Sporadic Colorectal Cancer Patients - Jin C. Kim; Seon A. Roh; Kum H. Koo; In H. Ka; Hee C. Kim; Chang S. Yu; Kang H. Lee; Jung S. Kim; Han I. Lee; Walter F. Bodmer (Familial Cancer, 2004)

p16 Expression in Squamous Lesions of the Female Genital Tract - Mary M. Finegan; Aaron C. Han; Mitchell I. Edelson; Norman G. Rosenblum (Journal of Molecular Histology, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Nitrous Oxide Emission and Urease Activity in Wheat - H. Bai; Y. Zhang; J. Han; C. Li (Bulletin of Environmental Contamination and Toxicology, 2003)

Determination of Semivolatile Compounds in Drinking Water by Tandem Mass Spectrometric Detection - L. Wang; Z. Huang; W. Zhou; C. Zhou; S. Han; A. Zhang; F. Feng; C. Liu (Bulletin of Environmental Contamination and Toxicology, 2003)

New designs for cancer vaccine and artificial veto cells - Mark L. Tykocinski; Aoshuan Chen; Jui-Han Huang; Matthew C. Weber; Guoxing Zheng (Immunologic Research, 2003)

Book Reviews: Forest Hydrology: An Introduction to Water and Forests - Richard C. Schultz; Kye-Han Lee (Forest Science, 2003)
In recent years, water resource issues concerning quality, quantity, and timing have been dominating natural resource management discussions around the world. Forest hydrology has historically been an important topic in forest management leading to some of the earliest forest research conducted in the United States. While there are a few textbooks on forest hydrology, there has always been a dilemma in what to include in such books. The hydrologic cycle may be briefly covered in ecology courses. However, without a significant introduction to water resources, most forestry and nonforestry students who enroll in a forest hydrology course do not have sufficient background in water resources to really understand the effect forests have on water quality, quantity and timing. A textbook for most forest hydrology courses should not only cover topics on forest impacts on water but also provide the basics of water properties, movement, and storage in the atmosphere, soil matrix, and surface water bodies. Putting both major topic areas in one manageable textbook requires trade-offs that do not dilute either subject area too much, but rather skillfully blend the two together. Mingteh Chang has done just that in writing this book.

Predicting atmospheric biases for real-time ambiguity resolution in GPS/GLONASS reference station networks - L. Dai; J. Wang; C. Rizos; S. Han (Journal of Geodesy, 2003)

Degradation of Ethoprophos in Three Physicochemically Different Soils Treated with Composted Manure and Chemical Fertilizer - S.-H. Yoo; K.-H. Han; C.-S. Kim; H.-M. Ro; S.-M. Lee (Bulletin of Environmental Contamination and Toxicology, 2003)

A critical review of vascular endothelial growth factor (VEGF) analysis in peripheral blood: Is the current literature meaningful? - E. Hormbrey; P. Gillespie; K. Turner; C. Han; A. Roberts; D. McGrouther; A.L. Harris (Clinical & Experimental Metastasis, 2002)

The complete nucleotide sequence of Beet black scorch virus (BBSV), a new member of the genus Necrovirus - Y. Cao; Z. Cai; Q. Ding; D. Li; C. Han; J. Yu; Y. Liu (Archives of Virology, 2002)

The exotic American eel in Taiwan: ecological implications - Y.‐S. Han; C.‐H. Yu; H.‐T. Yu; C.‐W. Chang; I‐C. Liao; W.‐N. Tzeng (Journal of Fish Biology, 2002)
Six American eels Anguilla rostrata were identified in the Kaoping River of south‐western Taiwan by sequencing the mitochondrial cytochrome b gene ( mtCyt‐b ). This was the first record of an exotic eel species in the natural waters of Taiwan. The exotic eels may have been imported from North America at the elver stage for aquaculture and escaped from culture ponds.

Self-organization in collective honeybee foraging: emergence of symmetry breaking, cross inhibition and equal harvest-rate distribution - Han de Vries; Jacobus C. Biesmeijer (Behavioral Ecology and Sociobiology, 2002)

Pathogenicity and vaccine efficacy of a thymidine kinase gene deleted infectious laryngotracheitis virus expressing the green fluorescent protein gene - M. G. Han; C. H. Kweon; I. P. Mo; S. J. Kim (Archives of Virology, 2002)

Allocation in recycling systems - Joost G. Vogtländer; Han C. Brezet; Charles F. Hendriks (The International Journal of Life Cycle Assessment, 2001)

From simulation to implementation: low-cost densification of permanent GPS networks in support of geodetic applications - H.-Y. Chen; C. Rizos; S. Han (Journal of Geodesy, 2001)

Correlation of Reversed-Phase Retention Factors for α-Branched Phenylsulfonyl Acetates with Octanol/Water Partition Coefficients and Quantum Chemical Descriptors - X. Liu; D. Wei; C. Wu; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 2001)

Workshop on Bioanalytical Methods Validation for Macromolecules: Summary Report - Krys J. Miller; Ronald R. Bowsher; Abbie Celniker; Jacqueline Gibbons; Shalini Gupta; Jean W. Lee; Steve J. Swanson; Wendell C. Smith; Russell S. Weiner; Daan J. A. Crommelin; Ira Das; Binodh S. DeSilva; et al. (Pharmaceutical Research, 2001)

Origin of laminated diatom ooze in King George Basin sediments from Bransfield Strait, Antarctica - H. I. Yoon; B. K. Park; M. W. Han; B. K. Khim; Y. Kim; C. Y. Kang (Geosciences Journal, 2001)

Physical and Chemical Properties of a Winter-Time Yellow Sand Event in Northeast Asia - B. G. Kim; J. Y. Ahn; H. R. Noh; C. J. Park; J. S. Han; S. U. Park (Water, Air, & Soil Pollution, 2001)

New Method to Calculate the N 2 Evolution from Mixed Venous Blood During the N 2 Washout - Decai Han; Duen-Ren Jeng; Julio C. Cruz; Xavier F. Flores; J. M. Mallea (Annals of Biomedical Engineering, 2001)

Accurate absolute GPS positioning through satellite clock error estimation - S.-C. Han; J. H. Kwon; C. Jekeli (Journal of Geodesy, 2001)

The virtual eco-costs ‘99 A single LCA-based indicator for sustainability and the eco-costs-value ratio (EVR) model for economic allocation - Joost G. Vogtländer; Han C. Brezet; Charles F. Hendriks (The International Journal of Life Cycle Assessment, 2001)

Identification of rice black-streaked dwarf fijivirus in maize with rough dwarf disease in China - S. Fang; J. Yu; J. Feng; C. Han; D. Li; Y. Liu (Archives of Virology, 2001)

Sequence variants and functional analysis of human papillomavirus type 16 E5 gene in clinical specimens - C.-H. Hsieh; Y.-P. Tsao; C.-H. Wang; C.-P. Han; J.-L. Chang; J.-Y. Lee; S.-L. Chen (Archives of Virology, 2000)

Adaptive filtering of continuous GPS results - L. Ge; H.-Y. Chen; S. Han; C. Rizos (Journal of Geodesy, 2000)

New applications of photoacoustics to the study of photosynthesis - Stephen K. Herbert; Tao Han; Thomas C. Vogelmann (Photosynthesis Research, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Diffusion-Convection Equation Solved in Parallel Regions of the Lung - Duen-Ren Jeng; Guoming Wu; Julio C. Cruz; Decai Han; Xavier F. Flores (Annals of Biomedical Engineering, 2000)

Host effect on genetic variation of Marssonina brunnea pathogenic to poplars - Z. M. Han; T. M. Yin; C. D. Li; M. R. Huang; R.L. Wu (Theoretical and Applied Genetics, 2000)

An Agrobacterium tumefaciens transformation protocol effective on a variety of cottonwood hybrids (genus Populus ) - K.-H. Han; R. Meilan; C. Ma; S. H. Strauss (Plant Cell Reports, 2000)

The nucleotide sequence of a Chinese isolate of wheat yellow mosaic virus and its comparison with a Japanese isolate - D. Li; L. Yan; N. Su; C. Han; Z. Hou; J. Yu; Y. Liu (Archives of Virology, 1999)

Roles of cyclin D1 and related genes in growth inhibition, senescence and apoptosis - E. K.-H. Han; S.-C. Ng; N. Arber; M. Begemann; I. B. Weinstein (Apoptosis, 1999)

QSAR for Polychlorinated Organic Compounds (PCOCs). I. Prediction of Partition Properties for PCOCs Using Quantum Chemical Parameters - J. Dai; C. Sun; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 1999)

Increased mRNAs for procollagens and key regulating enzymes in rat skeletal muscle following downhill running - Xiao-Yan Han; W. Wang; Satu O. A. Koskinen; Vuokko Kovanen; T. E. S. Takala; Jyrki Komulainen; Veikko Vihko; Philip C. Trackman (Pflügers Archiv - European Journal of Physiology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Detection and quantitation of a sodium-dependent sulfate cotransporter (NaSi-1) by sandwich-type enzyme-linked immunosorbent assay - Kazuko Sagawa; Debra C. DuBois; Bing Han; Richard R. Almon; Jürg Biber; Heini Murer; M. E. Morris (Pflügers Archiv - European Journal of Physiology, 1998)

Modelling collective foraging by means of individual behaviour rules in honey-bees - Han de Vries; Jacobus C. Biesmeijer (Behavioral Ecology and Sociobiology, 1998)

Estimation of Target Hazard Quotients and Potential Health Risks for Metals by Consumption of Seafood in Taiwan - B.-C. Han; W. L. Jeng; R. Y. Chen; G. T. Fang; T. C. Hung; R. J. Tseng (Archives of Environmental Contamination and Toxicology, 1998)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)

Strategies for the improvement of salidroside production in cell suspension cultures of Rhodiola sachalinensis - J. F. Xu; C. B. Liu; A. M. Han; P. S. Feng; Z. G. Su (Plant Cell Reports, 1998)

Rock-Shells ( Thais clavigera ) as an Indicator of As, Cu, and Zn Contamination on the Putai Coast of the Black-Foot Disease Area in Taiwan - B. C. Han; W. L. Jeng; M. S. Jeng; L. T. Kao; P. J. Meng; Y. L. Huang (Archives of Environmental Contamination and Toxicology, 1997)

Biomass accumulation and allocation in soybean associated with genotypic differences in tolerance of nitrogen fixation to water deficits - Larry C. Purcell; Manjula de Silva; C. Andy King; Wook Han Kim (Plant and Soil, 1997)

Murine Hn1 on Chromosome 11 is expressed in hemopoietic and brain tissues - Wozhan Tang; Yong-Hong Lai; Xiao-Dong Han; Peter M. C. Wong; Luanne L. Peters; David H. K. Chui (Mammalian Genome, 1997)

Chirp (2–7 kHz) echo characters in the Ulleung Basin - S. K. Chough; S. H. Lee; J. W. Kim; S. C. Park; D. G. Yoo; H. S. Han; S. H. Yoon; S. B. Oh; Y. B. Kim; G. G. Back (Geosciences Journal, 1997)

The longitudinal development of running economy in males and females aged between 13 and 27 years: The Amsterdam Growth and Health Study - Geertje A. M. Arins; Willem van Mechelen; Han C. G. Kemper; Jos W. R. Twisk; Willem van Mechelen (European Journal of Applied Physiology, 1997)

210 Pb-derived sediment accumulation rates in the southwestern East Sea (Sea of Japan) - G. H. Hong; S. H. Kim; C. S. Chung; D.-J. Kang; D.-H. Shin; H. J. Lee; S.-J. Han (Geo-Marine Letters, 1997)

Identification of a rat brain gene associated with aging by PCR differential display method - Han C. Wu; Eminy H. Y. Lee (Journal of Molecular Neuroscience, 1997)

Effect of EHS matrix on expression of transgenes in HC11 cells - T. H. Lee; M. G. Baik; W. B. Im; C. S. Lee; Y. M. Han; S. J. Kim; K. K. Lee; Y. J. Choi (In Vitro Cellular & Developmental Biology - Animal, 1997)

Two partial deletion mutations involving the same Alu sequence within intron 8 of the LDL receptor gene in Korean patients with familial hypercholesterolemia - Jae Jin Chae; Young Bae Park; Sung Han Kim; Sung Soo Hong; Gyun Jee Song; K. H. Han; Yong Namkoong; Hyo Soo Kim; C. C. Lee (Human Genetics, 1997)

Human Papillomavirus is More Prevalent in First Trimester Spontaneously Aborted Products of Conception Compared to Elective Specimens - P L Hermonat; L Han; P J Wendel; J G Quirk; S Stern; C L Lowery; T M Rechtin (Virus Genes, 1997)

Numerical bifurcation analysis of distance-dependent on-center off-surround shunting neural networks - Maartje E. J. Raijmakers; Han L. J. van der Maas; Peter C. M. Molenaar (Biological Cybernetics, 1996)

Monitoring lead pollution near a storage battery recycling plant in Taiwan, Republic of China - C. -Y. Yeh; H. -Y. Chiou; R. -Y. Chen; K. -H. Yeh; W. -L. Jeng; B. -C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Monitoring Lead Pollution Near a Storage Battery Recycling Plant in Taiwan, Republic of China - C.-Y. Yeh; H.-Y. Chiou; R.-Y. Chen; K.-H. Yeh; W.-L. Jeng, B.-C. Han (Archives of Environmental Contamination and Toxicology, 1996)

A neural network algorithm for the multiple traveling salesmen problem - E. Wacholder; J. Han; R. C. Mann (Biological Cybernetics, 1989)

Nucleotide sequence of the human? 1-globin gene - J. M. Gonzalez-Redondo; I. S. Han; Y. -C. Gu; T. H. J. Huisman (Biochemical Genetics, 1988)

The genetics of glutamic-pyruvic transaminase in mice: Inheritance, electrophoretic phenotypes, and postnatal changes - Shi-Han Chen; Roger P. Donahue; C. Ronald Scott (Biochemical Genetics, 1973)